Application of molasses improves strawberry marketability by enhancing fruit flavor and aroma - Yuanxiu Lin; Yu Long; Zimeng Cui; Siqi Dai; Yunting Zhang; Mengyao Li; Qing Chen; Yong Zhang; Haoru Tang; Yifei Zhou; Ya Luo (Postharvest Biology and Technology, 2026)

Regulatory mechanism of combustion and emission for ammonia direct injection engines by coupling thermal insulation coating with EGR strategy - Pengbo Dong; Yuxuan Liu; Kunlong Liu; Jiangping Tian; Wuqiang Long; Zechuan Cui; Liyun Fan; Zhenxian Zhang; Qingyang Wang (Fuel, 2026)

The spatiotemporal-specific regulation of cell wall–related proteins promotes the secretion of pigments in Antarctic fungi Geomyces sp. wnf-18c - Jiawen Du; Long Liu; Jiawen Gao; Xiaofeng Zhu; Lingkai Kong; Ting Cui; Menghao Cai; Xuemei Li; Yunxia Zhao; Xinyu Lu; Nengfei Wang; Shusheng Zhang (Bioresource Technology, 2026)

Effects of different feeding methods on the intestinal microbiota of Xizang sheep - Ayesha Khan; Jing Wu; Xiaoming Zhang; Jianzhao Cui; Khuram Shahzad; Hua Long; Quzong Deji; Baimaciren; Zhaxijiacai; Tianzeng Song; Wangsheng Zhao; Yangzong Zhaxi (Small Ruminant Research, 2026)

Quaternary evaporite sedimentation and potassium enrichment mechanism in Mahai Salt Lake, Qaidam Basin - Zihao Cui; Yanjun Zhao; Chenglin Liu; Pengyu Long; Yufei Hu; Ju Jiao; Jingjing Liu (Sedimentary Geology, 2026)

Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

What technologically proficient communities want from V2X: transport–environment implications from online discussions - Ondrej Havran; David Watling; Haibo Chen; Wen-Long Shang; Ye Liu; Chenxi Wang; Zhao Wang; Dingsong Cui; Dongyao Jia (Travel Behaviour and Society, 2026)

Study on the size effect model of mode I fracture characteristics in Longmaxi formation shale based on DIC and acoustic emission technology - Yu Suo; Xian-hang Wei; Gui-quan Wang; Cui-long Kong; Guang-chao Zhang; Xi Chen; Xiaofei Fu; Zhe-jun Pan; Bin Huang (Soil Dynamics and Earthquake Engineering, 2026)

Post-cyclic simple shear responses of soft clay under equivalent sequential seismic loading with various degrees of reconsolidation - Long-Ji Zhang; Zhen-Dong Cui; Meng-Hui Huang (Soil Dynamics and Earthquake Engineering, 2026)

Discovery of garnet-bearing peraluminous ferroan granites in the Trans-North China Orogen: Evidence for anatexis of residual metasedimentary crust in a hot collisional orogen - Jing-Jing Fan; Caiyun Lan; Yong-Min Li; Jun Rao; Zi-Long Wang; Ze-Xian Cui; Meng-Jing Li; Xiaoping Long (Precambrian Research, 2026)

Constructing Cu0-Cu+ sites inside carbon matrix for Fenton-like degradation of oxytetracycline and reduction of aromatic nitro compounds - Ye-Xia Li; Duo-Wei Ma; Bo Liu; Wen-Long Duan; Tian-Fang Cui; Lei Zhang; Jian Luan (Journal of Environmental Chemical Engineering, 2026)

Microglial Immunometabolic Remodeling After Ischemic Stroke: The Interplay Between Mitochondrial Stress and the Ischemic Microenvironment - Cui Liu; Qiang Liu; Weiyao Jing; Limei Liu; Long Wei; Xing Li; Xiaozheng Du (Translational Stroke Research, 2026)

From structural remodeling to cytoprotection: pH-regulated assembly of walnut protein hydrolysate fibril-chlorogenic acid complexes and transcriptomic insights - Chang Li; Jiangjuan Yuan; Junyang Long; Feng Jin; Baokai Cui; Jingzhen Chen; Changzhu Li; Fengjun Wang (Food Bioscience, 2026)

Near-complete phosphorus valorization from sewage sludge: Cost-effective co-production of vivianite and bioavailable detoxified hydrochar via a recyclable citric acid-mediated hydrothermal process - Xiaohan Cui; Yumeng Jin; Jian Zhu; Zhiyi Sun; Changkai Yin; Changfu Yang; Meifang Li; Long Kong; Chuansheng Chen; Zhihang Yuan; Ziyang Lou (Water Research, 2026)

Site-specific associations between soil methylmercury accumulation and plant, soil, and hgcA-associated microbial modules across Chinese coastal wetlands - Yuechen Tan; Weiwei Liu; Xu Pan; Songyuan Long; Yukun Hu; Lijuan Cui; Manyin Zhang (Journal of Hazardous Materials, 2026)

Antiviral functional divergence between two duplicated sting homeologs in amphitriploid gibel carp - Yue Wu; Shun Li; Chu-Jing Zhou; Bao-Jie Cui; Xiao Xu; Yang-Yang Wang; Yang Wang; Zhong-Wei Wang; Jian-Fang Gui; Long-Feng Lu; Li Zhou (Fish & Shellfish Immunology, 2026)

Bioinspired core-shell structured electrospun fibers guide neural stem/progenitor cell lineage development for spinal cord injury repair - Jiaxin Chen; Zilong Rao; Rui Cui; Rongli Deng; Jing Zhou; Daping Quan; Xipeng Guan; Houqing Long; Ying Bai (Chemical Engineering Journal, 2026)

Enhancement of comprehensive performances on electrical and waterproof properties for cellulose insulating paper with plasma treatment - Xinglei Cui; Zhonglian Li; Long Li; Lei Zhu; Honghua Xu; Xi Zhu; Zhi Fang (Chemical Engineering Journal, 2026)

Multi-site synergistic network-regulated succinonitrile gel polymer electrolyte for lithium metal batteries - Yang Yin; Yifan Xu; Yajie Hu; Kai Chen; Yupeng Feng; Jialin Wang; Tianhao Zhao; Tianyou Lan; Wei Yang; Qi Liu; Xingbo Guo; Shubiao Xia; et al. (Chemical Engineering Journal, 2026)

A circular agriculture model based on vegetable tailing fermentation broth: a case study of cabbage production - Junjie Cui; Rongrong Zhang; Mingle Yang; Tingting Mu; Shilei Luo; Long Li; Guobin Zhang (Bioresource Technology Reports, 2026)

Spatiotemporal footprints and health risk assessments of odor emissions from large-scale food waste anaerobic digestion plants - Lin Cui; Ziyang Lou; Long Kong; Farooq Muhammad Amjad; Zhijie Wang; Changfu Yang; Jun Si; Meilan Zhang; Luochun Wang; Zhaowen Cheng (Atmospheric Environment, 2026)

Environmental controls on methyl tert-butyl ether (MTBE) interphase redistribution in compacted low-permeability soils - Meng Wang; Kangping Cui; Long Xu; Fusheng Zha; Qiao Wang; Jinkun Huang; Jingjing Liu (Applied Geochemistry, 2026)

Predicting big five personality traits from resting-state EEG connectivity: a connectome predictive modeling study - Chu Zhang; Yao Liu; Yiting Long; Siyuan Hu; Ming Li; Wenkai Bai; Yiting Li; Can Cui; Can Gao (Brain Structure and Function, 2026)

Green and efficient maize varieties synergize global yield and nitrogen sustainability - Xun Wei; Yulong Yin; Xueqin Zhu; Ziwen Li; Zhenying Dong; Yan Long; Yanbo Wang; Jiuran Zhao; Changling Huang; Xingming Fan; Huabang Chen; Pervez H. Zaidi; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Prediction of Arctic sea ice concentration and thickness using a cross-attention enhanced PredRNN - Teng Long; Jinli Xiao; Hailong Cui; Huanhuan Li; Zaili Yang; Yaqing Shu (Ocean Engineering, 2026)

Corrigendum to “Catechol-induced assembly to enhance the performance of antimicrobial peptide fully” [Chem. Eng. J. Volume 524 (2025) 169195] - Xiao Wang; Yuanyuan He; Beibei Cui; Yuan Feng; Jingjing Lin; Xirui Long; Yanchao Wang; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2026)

Biomimetic and flexoelectric high-entanglement single-polymer polyampholyte hydrogel via consecutive photopolymerization - Guohao Li; Jiaqian Nong; Dapeng Li; Zhaoliang Cui; Yiwan Huang; Shijun Long; Xuefeng Li (Chemical Engineering Journal, 2026)

Compatibility of three adjuvants with Cordyceps fumosorosea and their synergistic effects on controlling the diamondback moth, Plutella xylostella - Mei-Qiong Xie; Long-Jiang Wang; Yong-Qiang Han; Jin-Cui Chen; Li-Ying Cao; Shi-Chuan Luo; Fan-Fan Jiao; Shu-Jun Wei (Crop Protection, 2026)

Empirical evaluation of battery swapping technology adoption in urban electric taxi operations - Dingsong Cui; Haibo Chen; David Watling; Ye Liu; Wen-Long Shang; Chenxi Wang; Peng Liu; Chengcheng Xu; Dimitris Margaritis (Transportation Research Part D: Transport and Environment, 2026)

Deactivation mechanisms of spent V-Ti-based SCR catalysts and strategies for resource utilization: A systematic review - Jinrong Ju; Shitong Cui; Zhengyu Liu; Wei Yang; Tao Long; Sha Deng (Process Safety and Environmental Protection, 2026)

The molecular regulatory network for the accumulation of metabolites in the stems and roots of Ephedra sinica by the fungus Didymella keratinophila - Xin-Yan Sun; Wen Li; Hai-Xia Zhao; Jin-Long Cui (Physiological and Molecular Plant Pathology, 2026)

Mean warming enhances insect resilience to high temperatures: species-specific evidence from two wheat aphids - Xue-Jing Wang; Yu Wang; Shu-Lin Ning; Jia-Qi Li; Biao Cui; Long-Fei Yue; Li-Yan Wang; Chun-Sen Ma (Journal of Insect Physiology, 2026)

Cerrena unicolor laccases as sustainable biocatalysts for detoxifying hazardous long-chain phthalates and deconstructing plastic mulch films - Long-Bin Zhang; Jun Kang; Xiu-Gen Qiu; Zhou Cui; Yu-Tian Li; Yan Zheng; Yu Li; Yi Guan; Juan-Juan Yang; Chun Meng (Journal of Environmental Management, 2026)

Saltiness enhancement of microwave-heated gel matrix focused on Na+ “burst” release behavior and matrix fragmentation during oral processing - Min Zhang; Yaqi Hou; Shuqin Xia; Song Miao; Khizar Hayat; Heping Cui; Jingyang Yu; Shahzad Hussain; Long Zhang (Food Research International, 2026)

Effect of pile foundation on seismic response of adjacent subway station buried in sand site by centrifuge shaking table tests - Long-Ji Zhang; Zhen-Dong Cui; Meng-Hui Huang; Jia-Sen Yan; Su-Yang Wang (Engineering Structures, 2026)

Enhanced tolerance of triploid Betula pendula ‘Purple Rain’ to short-term chilling stress is associated with antioxidant capacity and BpSOD gene expression - Jie Zhang; Jingnan Li; Shicheng Li; Ling Lin; Long Liu; Xiaoyue Zhang; Ying Cui; Yujun Zhou; Jing Jiang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Transitioning from landfill to cross-regional centralized recycling: Uncovering the mechanisms and potentials of hard-to-treat hazardous waste through medical waste incineration fly ash recycling - Wu Su; Yao Wang; Xiao Cui; Yueyue He; Jun Zhao; Long Wen; Guangren Qian (Waste Management, 2026)

Tuning CO2 separation of Type I UiO-66 porous liquids by varying the size of porous hosts - Shuangshuang Long; Jingwen Wang; Shuqian Meng; Yaxin Liu; Jing Zhang; Zihao Ren; Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Libing Qian; Wenwu Zhou; et al. (Journal of Environmental Chemical Engineering, 2026)

On-demand amorphous calcium phosphate-mediated regeneration of dentin and enamel using ion-regulated hydroxypropyl methylcellulose and carboxymethyl chitosan hydrogels - Zihan Cui; Zhiwen Liu; Zhixin Zhang; Danni Wang; Taoyu Chen; Baiping Fu; Ling Zhu; Long Zhao; Zhe Wang (Carbohydrate Polymers, 2026)

In vitro regeneration of Lily bulblets and artificial seeds development - Zhengjing Wu; Yuan Long; Luping Cui; Mengting Ma; Xun Liu; Zijing Lin; XinYi Wu; Yifang Su (Journal of Plant Biochemistry and Biotechnology, 2026)

Spatial variations and driving factors of soil microbial traits in healthy and unhealthy Populus euphratica along riparian gradients - Reyila Mumin; Wen Zhao; Kaichuan Huang; Long Zeng; Dongmei Wu; Neng Gao; Junning Li; Asadilla Yusup; Yifei Sun; Baokai Cui (Soil Ecology Letters, 2026)

EGR1 regulates degranulation and mediator release in C48/80-induced pseudo-allergic reactions - YiZhao Sun; Heng Li; Juntao Li; YaoJun Wang; Tongyun Long; Zhe Cui; Yanfen Zhang; Zhongcheng Liu (Immunologic Research, 2026)

Two new abietane-type diterpenoids from the roots of Tripterygium wilfordii Hook.f. and their diacylglycerol acyltransferase activity - Hao Xu; Xue-Feng Wu; Ying-Xiao Xiao; Yuan Gao; Yi-Lin Li; Hyun-Sun Lee; Long Cui (Natural Product Research, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

TTM: A concise yet effective surface reconstruction approach for tunnel point cloud from mobile mapping system - Hao Cui; Jian Li; Qingwu Hu; Long He; Yiwen Tao; Lei Xu; Qingzhou Mao (Tunnelling and Underground Space Technology, 2026)

Near-Zero NH3/N2O emissions enabled in two-stroke ammonia-diesel dual-direct-injection engines: an experimental study via synergistic diesel multiple injection strategy - Weize Chen; Jingchen Cui; Zhenxian Zhang; Qingyang Wang; Pengbo Dong; Xiangyu Meng; Jiangping Tian; Hua Tian; Wuqiang Long; Shiying Liu (Fuel, 2026)

Transcriptomic analysis of the dynamic changes in polysaccharide biosynthesis metabolism in Lentinula edodes throughout liquid fermentation - Yanjie Li; Jing Wang; Ziwei Chen; Jingjing Wang; Long Chen; Nan Qin; Shuzhen Cui; Xinjie Guo (Fungal Biology, 2026)

Blackwellomyces napialus (Cordycipitaceae, Hypocreales), a Novel Species Parasitic on Napialus hunanensis from China - Jin-Long Jia; Cui-Yuan Wei; Mei Tang; Zhu-Yu Cheng; Ya-Nan Wang; Zhu-Liang Yang; Gang Deng; Yuan-Bing Wang (Current Microbiology, 2026)

Effects of Inverse Solutions and Calibration Errors on Localization Performance of OPM-MEG - Shengjie Qi; Shuhao Cui; Le Jia; Tengyue Long; Xinda Song; Xiaolin Ning (Annals of Biomedical Engineering, 2026)

Dynamics of leaf litter decomposition and nutrient release in mangroves under different control conditions: Highlighting the litter quality, decomposer and mixing effect - Jianxiang Feng; Lixia You; Xinyi Gao; Manman Liu; Weiying Zhao; Yulan Wu; Xiaowei Cui; Meilin Wu; Long Wei (Marine Pollution Bulletin, 2026)

Integrated QTL mapping and functional analysis reveal GmDWF4.2 as a key regulator of soybean plant height - Lijuan Ai; Qiang Chen; Yuxin Liu; Cunyi Sun; Xiaolei Shi; Chunjiang Zhou; Sujuan Cui; Hongtao Zhao; Long Yan; Chunyan Yang (Plant Science, 2026)

A federated learning-based Aflatoxin M1 prediction model under a data enhancement strategy - Long Wang; Xiaodong Song; Haohan Ding; Xiaohui Cui; David I. Wilson; Wei Yu; Yinghao Yang; Guanjun Dong (Journal of Food Engineering, 2026)

The characteristics of metabolites accumulation and their connections with endophytic fungi in roots and stems of Ephedra sinica with different cultivation ages - Shan-Shan Wang; Xin Ji; Jun-Hong Wang; Yuan-Peng Hao; Jin-Long Cui (Fungal Biology, 2026)

Spatiotemporal Variability of China's 800 mm Precipitation Isohyet (1961–2022): Multi-scale Analysis of its Migration and Impact on Hydroclimatic Extremes - Shaowei Ning; Le Chen; Rujian Long; Yuliang Zhou; Yi Cui; Min Zhang; Lichang Xu; Juliang Jin; Thapa bthapa (Atmospheric Research, 2026)

Fiber optic monitoring technology (FBG) on the deformation law of reinforced retaining wall - Tingya Han; Jianhui Long; Shiyi Guo; Chengji An; Hangyu Weng; Zhiqiang Yi; Lipeng Cui (Journal of Mountain Science, 2026)

Composition characterization of the culturable endophytic fungi in roots and their antagonistic activity against root rot of Astragalus mongholicus - Zhong-Ya Zhou; Xi Liu; Fen Gao; Meng-Liang Wang; Jun-Hong Wang; Jin-Long Cui (Archives of Microbiology, 2026)

Dissecting the aberrant vasculature of glioblastoma: mechanisms and therapeutic targets - Yinan Li; Yinfei Du; Fan Guan; Xuetong Li; Shu Cui; Wei Gao; Xinmiao Long; Minghua Wu (Cancer and Metastasis Reviews, 2026)

Can nighttime light proxy comprehensive economic well-being? Evidence from China - Wei Jiang; Jie Liu; Tengfei Long; Ming Liu; Akiyuki Kawasaki; Zhiguo Pang; Denghua Yan; Yizi Shang; Elhadi Adam; Xiaohui Ding; Shiai Cui (Sustainable Cities and Society, 2026)

High-loading single-atom photocatalysts for high-selectivity conversion of CO2 to ethanol - Long-Shuai Zhang; Feiyao Wu; Shenrui Liang; Qianqian Tang; Hui Li; Huang Zhou; Fanqi Meng; Xunheng Jiang; Haiyan Liu; Qing Sun; Meifeng Wu; Yitao Cui; et al. (Science Bulletin, 2026)

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

Visualization study on combustion characteristics of direct-injection methanol ignited by micro-injection diesel in a hydrogen-rich syngas atmosphere - Yuanyou Tang; Wuqiang Long; Zhizhuo Dai; Zechuan Cui; Yang Wang; Ge Xiao; Pengbo Dong; Hua Tian (Fuel, 2026)

Numerical optimization of injection strategy for methanol engine with glow plug hot surface ignition system - Chunyang Xie; Yongjian Wang; Wuqiang Long; Pengbo Dong; Yang Wang; Jingchen Cui; Hua Tian; Wenliang Lu (Fuel, 2026)

Predicting suitable habitats and carbon storage potential of mangroves: A case study in Zhanjiang, China - Zeyu Lin; Wenxiao Su; Xiaowei Cui; Long Wei; Jianxiang Feng (Ecological Engineering, 2026)

A dual closed-loop CO2 mineralization system with multicycle stability: Sustainable production of CaCO3 and upgrading supplementary cementitious materials via amino acid selective leaching - Xuan Zheng; Long Ji; Yang Xu; Liang Li; Qiufang Cui; Shuiping Yan (Chemical Engineering Journal, 2026)

Tailoring metal-support interaction boosted thermal catalytic heterolytic hydrogenation for biomass upgrading - Dongying Yan; Long Cui; Weifeng Fan; Ruihui Gan; Chenxi Bai (Chemical Engineering Journal, 2026)

Effects of intercropping Eleutherococcus senticosus on the photosynthesis, active ingredient content and soil microbial community composition of Arisaema amurense - Jiapeng Zhu; Yanmei Cui; Cai Shao; Bochen Lv; Weiyu Cao; Hongjie Long; Yayu Zhang; Hai Sun (Plant and Soil, 2026)

Characteristics and contribution of VOCs emission from motorcycles to ozone formation in Xi’an, China - Wanli Yuan; Yongjie Lv; Jiahui Qu; Baoji Li; Yongfang Rao; Ou Ji; Long Cui; Yu Huang (Aerosol Science and Engineering, 2026)

Elucidating the role of Alg14 in governing cell wall architecture and biological functions in the entomopathogenic fungus Beauveria bassiana - Long-Bin Zhang; Yu-Tian Li; Zhi-Hao Yang; Zhou Cui; Yi Guan; Guang-Hui Liu (Pesticide Biochemistry and Physiology, 2026)

Phragmalin-type limonoid orthoesters from the twigs and leaves of Khaya ivorensis and their cytotoxic activities - Zong-Yi Zhang; Jia-Nan Wang; Peng Sun; Xiao-Cui Shi; Yi-Dian Xiao; Kai-Long Ji; Chun-Fen Xiao; Xiao-Nian Li; You-Kai Xu; Dong-Hua Cao (Phytochemistry, 2026)

The effect of pet dog exposure on gut antibiotic resistome and microbiome of their owners - Wenjing Cui; Yange Cui; Yuqing Hao; Yuan Li; Ying Wang; Fang Liu; Jinzhao Long; Yuefei Jin; Shuaiyin Chen; Guangcai Duan; Haiyan Yang (Journal of Hazardous Materials, 2026)

The multi-carboxyl metal-organic framework MIL-101(Fe) effectively adsorbs total purines from whole soybean seeds - Deshuai Shao; Cui He; Na Li; Yuqing Gao; Xiaoyu Hu; Yingrun Cai; Qinqin Zhang; Jiahui Yao; Shuo Wang; Yifan Yang; Jiayi Pan; Huihui Gao; et al. (Food Chemistry, 2026)

Synthesis of sustainable green bio-polycarbonates from bio-based feedstock and CO2 toward carbon–neutral goals: opportunities and challenges - Jiarong Tian; Siyuan Zhang; Ziyang Wang; Mehrdad Adl; Long Lin; Huseyin Guler; Shaoqing Cui (Bioresource Technology, 2026)

Improvement of air quality from upgradation of aged diesel vehicles: A case study in Northwest China - Yonggang Xue; Gangzhu Zhang; Liqin Wang; Long Chen; Long Cui; Yu Huang; Junji Cao (Atmospheric Environment, 2026)

Seismic performance of beam-column joints reinforced with ECC - Long Liu; Hongbo Xiao; Songqiang Wan; Chunling Yan; Yu Wang; Chong Liu; Xiaoze Yang; Liang Cui; Chenjie Hao; Menghao Ming; Boyang Liu; Yingying Bi (Bulletin of Earthquake Engineering, 2026)

Research on fault differentiation methods for similar faults based on multiple Gated memory graph convolutional networks (M−GM−GCN) - Zhanguo Ma; Long Tian; Liang Zhang; Wenhao Jia; Jing Cui; Ziyang Cui; Dihao Zheng (Annals of Nuclear Energy, 2026)

Near-full-component sewage sludge valorization via integrated alkali-mediated pyrolysis and sub-boiling temperature crystallization of hierarchical carbon-zeolite composites from carbonaceous and inorganic constituents - Zhihang Yuan; Houmin Yin; Jicui Cui; Changfu Yang; Zhou Zhen; Xiaohan Cui; Yumeng Jin; Lifeng Lin; Long Kong; Ruina Zhang; Ruyi Wang; Lei Che; et al. (Water Research, 2026)

Last-mile transit PM2.5 under ultra low emission zone: a network-based exposure assessment - Qi Long; Jun Ma; Cui Guo; Feifeng Jiang (Transportation Research Part D: Transport and Environment, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Spatiotemporal evolution and resilience optimization of urban ecological networks: A case study of the Xiong'an New Area - Lixiang Wen; Junhong Bai; Yuejing Rong; Langying Long; Changhong Xiao; Yanan Guan; Baoshan Cui (Journal of Cleaner Production, 2026)

Corrigendum to ‘Metabolic flexibility of rhizobacteria drives soil nutrient cycling and enhances rare earth elements hyperaccumulation in ferns colonizing degraded mine ecosystems’ [J. Environ. Manag. 395 (2025) 128013] - Yong-He Han; Xi-Wen Cui; Hai-Bin Han; Yang-Long Jiang; Li-Chao Tong; Jian-Fei Chen; Hong Zhang; Yong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

Hyporheic descending flow inhibited microbial phosphate mineralization and sulfur oxidation, thus suppressing sediment phosphorus release - Yue Qu; Jinxi Song; Yongqing Long; Ken Qin; Qifan Cui (Journal of Environmental Management, 2026)

Microwave-assisted synthesis of CQDs/ZnO hollow microspheres for complete NO oxidation under visible light - Yan Liu; Xianjin Shi; Long Cui; Pengge Wang; Zhenbo Zhang; Li Chen; Zhenyu Wang (Journal of Environmental Sciences, 2026)

Coupling study on the effects of ammonia energy ratios and injector relative positions on the performance of an ammonia/diesel dual-direct-injection two-stroke engine - Jingchen Cui; Weize Chen; Wuqiang Long; Hua Tian; Shuo Liu; Zhenxian Zhang (Fuel, 2026)

Autophagic degradation of MAVS-B by Carassius auratus herpesvirus (CaHV) ORF56 suppresses interferon response in polyploid gibel carp - Chu-Jing Zhou; Can Zhang; Long-Feng Lu; Bao-Jie Cui; Xi-Yin Li; Li Zhou; Shun Li; Jian-Fang Gui (Fish & Shellfish Immunology, 2026)

Experimental study on the cyclic and post-cyclic monotonic behavior of soft clay under equivalent seismic loading - Zhong-Liang Zhang; Zhen-Dong Cui; Long-Ji Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Correction: Highly Sensitive “On-off” Fluorescent Probe TPA-DNBS Based on Triphenylamine Derivative for Selective Detection of Cysteine - Siyi Wei; Yanqing Xu; Qian Long; Haotian Xie; Wenqi Wu; Xueke Chen; Yan Lin; Hanfeng Cui (Journal of Fluorescence, 2025)

Response Design and Experimental Analysis of Marine Riser Buoy Observation System Based on Fiber Optic Sensing Under South China Sea Climatic Conditions - Lei Liang; Shuhan Long; Xianyu Lai; Yixuan Cui; Jian Gu (Journal of Marine Science and Engineering, 2025)
Marine risers, critical structures connecting underwater production systems and surface floating platforms, stand freely in water and endure extremely complex marine environmental loads. To meet the multi-parameter observation demand for their overall state, a fiber-optic sensing-based marine riser buoy observation system was developed. Unlike traditional point-type and offline monitoring systems, it integrates marine buoys with sensing submarine cables to achieve long-term real-time online monitoring of risers’ overall state via fiber-optic sensing technology. Comprising two main modules (buoy monitoring module and fiber-optic sensing module), the buoy’s stability was verified through theoretical derivation, simulation, and stability curve plotting. Frequency domain analysis of buoy loads and motion responses, along with calculation of motion response amplitude operators (RAOs) at various incident angles, showed the system avoids wave periods in the South China Sea (no resonance), ensuring structural safety for offshore operations. A 7-day marine test of the prototype was conducted in Yazhou Bay, Hainan Province, to monitor real-time temperature and strain data of the riser in the test sea area. The sensing submarine cable accurately responded to temperature changes at different depths with high stability and precision; using the Frenet-based 3D curve reconstruction algorithm, pipeline shape was inverted from the monitored strain data, enabling real-time pipeline monitoring. During the test, the buoy and fiber-optic sensing module operated stably. This marine test confirms the buoy observation system’s reasonable design parameters and feasible scheme, applicable to temperature and deformation monitoring of marine risers.

Silencing of the Superaquaporin LvAQP11 Disrupts Salinity Tolerance, Molting Cycle, and Myofibril Organization in Litopenaeus vannamei - Zhongkai Wang; Guanghao Song; Shikui Zhang; Long Zhang; Beibei Wang; Kunpeng Zhao; Yanting Cui; Fei Liu; Renjie Wang; Yuquan Li (Fishes, 2025)
The Pacific white shrimp (Litopenaeus vannamei), a euryhaline crustacean of significant economic importance, is widely cultivated for its adaptability to diverse salinity levels. Aquaporins (AQPs) are membrane channel proteins that mediate the transport of water and small solutes across biological membranes. Among them, aquaporin 11 (AQP11) is classified as a superaquaporin, and its physiological roles remain unclear. In this study, RNA interference (RNAi) was employed to silence AQP11 expression in L. vannamei, followed by RNA-seq analysis to investigate transcriptomic responses. Differentially expressed genes (DEGs) were identified by comparing dsAQP11 and control groups. The LvAQP11 knockdown significantly increased mortality to 76.7% under acute high-salinity stress (50‰) but not under low-salinity conditions (10‰). Transcriptomic analysis revealed that LvAQP11 deficiency disrupted amino acid metabolism pathways and triggered endoplasmic reticulum stress, as evidenced by the upregulation of proteasome subunits and unfolded protein response genes. Furthermore, silencing LvAQP11 delayed molting progression in the premolt stages, accompanied by the significant upregulation of molt-inhibiting hormone (LvMIH1/5) and downregulation of retinoic acid X receptor (LvRXR). The long-term silencing of LvAQP11 did not affect the weight gain rate (WGR) or the specific growth rate (SGR) but induced muscle fiber disorganization and significantly increased muscle water content. RNA sequencing identified enriched carbohydrate and chitin metabolism pathways, indicating disrupted cytoskeletal dynamics and extracellular matrix integrity. Through this study, we elucidate the crucial roles of LvAQP11 in osmoregulation, molting, and muscle integrity in L. vannamei, providing novel insights into the multifunctional nature of superaquaporins beyond water transport.

Room-Temperature Fabrication of Dual-Functional SiO2/TiO2 Coating for Photovoltaic Efficiency Enhancement: From Laboratory Development to Field Validation - Pengge Wang; Xinwei Li; Ning Zhang; Yue Zhai; Zhenyu Wang; Long Cui; Suixin Liu; Wingkei Ho; Yu Huang; Shun-cheng Lee (Aerosol Science and Engineering, 2025)

Using UAV multispectral image data to monitor the nitrogen status of head cabbage shoots in the Liupan Mountain area of China - Shuai Wang; Long-Guo Wu; Hua Ma; Kelsang Choron; Fu-Shun Zheng; Zhong-Ting Song; Cui Yin; Hong-Yan Zhu; Peng-Yuan Lv; Yun-e Cao (International Journal of Remote Sensing, 2025)

Global trends, hotspots and future prospects of ecological resilience of coastal wetlands: A bibliometric analysis - Changhong Xiao; Junhong Bai; Guozhu Chen; Langying Long; Jichen Qiu; Yuhao Xu; Tian Xie; Lijuan Cui (Marine Pollution Bulletin, 2025)

Formation and in-situ identification of unique microplastic-rock blends under anthropogenic thermal conditions - Changfu Yang; Qiujie Huang; Yuheng You; Zhihang Yuan; Hui Wang; Jicui Cui; Dong Ma; Long Kong; Nanwen Zhu; Ziyang Lou (Water Research, 2025)

A complex network perspective on urban heat regulation: Enhancing cold-heat exchange via link prediction - Huanjia Cui; Yu Wang; Qiang Yu; Buyanbaatar Avirmed; Jikai Zhao; Yilin Liu; Xinyu Yang; Bowen Chi; Ji Long (Urban Climate, 2025)

Soil amoeba richness drives local-scale bacterial and fungal community assembly - Haijing Hu; Fenggang Luan; Xiaodong Liu; Yina Jiang; Dianming Hu; Haozhi Long; Zhijun Zhai; Junqing Yan; Chaoyu Cui; Haiyan Song; Jianping Zhou; Gang He; et al. (Soil Biology and Biochemistry, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Fractal and particle flow analysis of brittle failure in lce under uniaxial compression: Temperature-dependent mechanisms - Jianlin Chang; He Yang; Guoqing Cui; Fanghui Shan; Xiang Long; Chun Tan; Pinlu Cao (Ocean Engineering, 2025)

Recycled oceanic crust restricting trace element enrichment in mid-ocean ridge basalts - Fan Yang; Xiao-Long Huang; Yi-Gang Xu; Yang Yu; Peng-Li He; Le Zhang; Ze-Xian Cui (Lithos, 2025)

Metabolic flexibility of rhizobacteria drives soil nutrient cycling and enhances rare earth elements hyperaccumulation in ferns colonizing degraded mine ecosystems - Yong-He Han; Xi-Wen Cui; Hai-Bin Han; Yang-Long Jiang; Li-Chao Tong; Jian-Fei Chen; Hong Zhang; Yong Zhang; Zhibiao Chen (Journal of Environmental Management, 2025)

Exploring spatiotemporal dynamics of urban flood socioeconomic exposure risk and driving factors under future precipitation change and urbanization scenarios - Wen Liu; Qi Feng; Yuwei Liang; Yanqiang Cui; Long Xu; Bernard A. Engel (Journal of Environmental Management, 2025)

Molecular mechanisms underlying microplastics-induced inhibition of lateral root development in tomato (Solanum lycopersicum L.) - Rongchao Yang; Mengjiao Chen; Long Cheng; Yilan Cui; Chengyong Li; Yueqin Zhang (Journal of Environmental Management, 2025)

Interface layer-assisted construction of metal organic framework based porous liquids for high performance CO2 selective separation - Zheng Dong; Yangyang Xin; Bowen Xiang; Ruilu Yang; Menglin Zhu; Baolu Cui; Chenjiao Xie; Shuangshuang Long; Wenwu Zhou; Jianwei Liu; Libing Qian; Hongze Guo; et al. (Journal of Environmental Chemical Engineering, 2025)

Synergistic effect of Ru-Ni nanoparticles supported on mesoporous carbon black for highly selective hydrogenation of nitrobenzene to aniline in aqueous phase - Shuo Li; Marcos Millan; Feng Gao; Xiangyi Long; Guanming Yuan; Zhengwei Cui (Fuel, 2025)

Xylo-oligosaccharide utilization by Weissella kandleri YT103: Transcriptomic analysis and intestinal barrier protection - Xin-rui Zhang; Shuang-shuang Cui; Long-fen Yin; Gui-zhen Gong; Jian-xia Yang; Yang Chen; Yuan-ting Zhu (Food Research International, 2025)

Shifts in microbial metabolic strategy drive reduced biomass-specific enzyme activity in mountain hazard-affected soils - Yufei Yao; Qihao Tao; Qifan Cui; Guowei Pang; Qifang Zhang; Yongqing Long; Lei Wang; Bing Xu; Jinxi Song (CATENA, 2025)

Distribution characteristics and relationships of soil organic carbon and inorganic carbon in a typical wetland in semi-arid area of Northeast China - Yuan Xin; Xianglong Xing; Long Chen; Zhongsheng Zhang; Walian Du; Shouzheng Tong; Mingye Zhang; Yu An; Geng Cui; Dongmei Zheng; Guangtao Liu (CATENA, 2025)

Experimental investigation on local scour evolution around a circular monopile in the silty bed under wave-current combinations - Chunguang Yuan; Mingxiao Xie; Jinquan Wang; Xiaoliang Xia; Long Xiao; Na Zhang; Cheng Cui (Coastal Engineering, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Fault diagnosis study for nuclear power plants under imbalanced fault sample datasets based on deep learning - Zhanguo Ma; Jing Cui; Jing Zhang; Liang Zhang; Wenhao Jia; Long Tian (Annals of Nuclear Energy, 2025)

Highly Sensitive “On-off” Fluorescent Probe TPA-DNBS Based on Triphenylamine Derivative for Selective Detection of Cysteine - Siyi Wei; Yanqing Xu; Qian Long; Haotian Xie; Wenqi Wu; Xueke Chen; Yan Lin; Hanfeng Cui (Journal of Fluorescence, 2025)

Microbial community dynamics and ecological interactions during an atypical winter Cerataulina pelagica (Bacillariophyta) bloom in Laizhou Bay, southern Bohai Sea - Long Yang; Hongwei Wang; Zhengguo Cui; Hualong Wang; Xiaokun Ding; Di Zhang; Huanyu Zhang; Sheng Li; Tao Jiang (Marine Environmental Research, 2025)

A new insight into the mechanism of DEHP-induced cardiotoxicity: Triggering pyroptosis of cardiomyocytes by disrupting sphingolipid metabolism - Jia-Gen Cui; Hao Zhang; Yue-Qi Zhang; Bing Sun; Xue-Nan Li; Yi Zhao; Jin-Long Li (Journal of Hazardous Materials, 2025)

Catechol-induced assembly to enhance the performance of antimicrobial peptide fully - Xiao Wang; Yuanyuan He; Beibei Cui; Yuan Feng; Jingjing Lin; Xirui Long; Yanchao Wang; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2025)

MOF-derived carbonaceous aerogel via water-induced self-assembly for tunable electromagnetic wave absorption - Xueting Zhang; Shaocong Zhong; Yuanshuai Wang; Muyao Liu; Yan'ni Yang; Miaoqiong Niu; Fangzhou Cui; Xinyu Wang; Yanan Yang; Long Xia (Chemical Engineering Journal, 2025)

Development of biodegradable starch-based lambda-cyhalothrin microcapsules for sustainable long-term pest control and enhanced utilization efficacy - Liang Li; Long Chen; Qian Du; Xiquan Ding; Hongyan Chen; Fei Gao; Bo Cui; Haixin Cui; Zhanghua Zeng (Carbohydrate Polymers, 2025)

Antagonistic interactions between hummock formation and microtopography in wetlands modulate soil seed bank dynamics via biotic-abiotic coupling - Mingye Zhang; Shuchen Liu; Shouzheng Tong; Yu An; Ming Jiang; Long Chen; Guodong Wang; Geng Cui; Dongjie Zhang (CATENA, 2025)

An interpretable deep transfer learning method for fault diagnosis of nuclear power plants under multiple power level conditions - Zhanguo Ma; Wenhao Jia; Long Tian; Jing Cui; Dihao Zheng; Ziyang Cui (Annals of Nuclear Energy, 2025)

Characteristics and mechanisms of summer subsurface marine heatwaves in the East/Japan Sea - Zhiyuan Li; Yan Cui; Gangfeng Wu; Dakang Liu; Gang Ren; Chang Xu; Yu Long; Xiao-Hua Zhu (Frontiers in Marine Science, 2025)
This study investigated the summer subsurface marine heatwaves (SSMHWs) in the East/Japan Sea (EJS) using the Japan Coastal Ocean Predictability Experiment 2 ocean reanalysis datasets during 1993–2023. Climatologically, the cumulative (maximum) intensity area-averaged over the EJS ranges from 20°C days (2.5°C) at surface to its maximum of 36°C days (4°C) at approximately 70 m, confirming significant subsurface intensification of summer MHWs. Compared with the almost uniform spatial patterns at surface, the intensities of MHWs at subsurface layers show substantial spatial variations. The SSMHWs in the EJS are caused not by surface atmospheric forcings, but primarily by internal oceanic processes. During summer, the strong stratification in the EJS inhibits the vertical mixing and traps more heat fluxes at surface. As the main heat sources of the upper ocean, the Tsushima Warm Current (TWC) plays a crucial role in triggering SSMHWs in the EJS. Anomalous increased volume transport of TWC carries more warm water into the EJS, favoring the basin-scale intense SSMHWs. This warm water is redistributed by the East Korean Warm Current and mesoscale eddies, leading to regional features of SSMHWs in the EJS. Our results highlighted the roles of oceanic circulation in forming intense SSMHWs in the EJS.

A new isoflavone glycoside from the stems of Eclipta prostrata (L.) L. with glycosidase inhibitory activity - Yuan Gao; Ying-Xiao Xiao; Hao Xu; Xue-Feng Wu; Yi-Lin Li; Hyun-Sun Lee; Long Cui (Natural Product Research, 2025)

Understanding aerosol pollutant generation in wet-mix shotcrete for tunnel construction - Kun-Hua Liu; Shu Wang; Jia-Wei Zhao; Zhen Guo; Sheng-nan Ou; Long-Zhe Jin; Jun-yong Cui (Tunnelling and Underground Space Technology, 2025)

Effect of initial static shear stress on cyclic properties of soft clay in constant volume simple shear tests - Meng-Hui Huang; Zhen-Dong Cui; Long-Ji Zhang (Soil Dynamics and Earthquake Engineering, 2025)

Energy-based evaluation of cyclic shear behaviors of soft clay under mainshock-aftershock sequence loading - Long-Ji Zhang; Zhen-Dong Cui; Meng-Hui Huang (Soil Dynamics and Earthquake Engineering, 2025)

A novel chemical constituent from the stems of Akebia quinata and its diacylglycerol acyltransferase inhibitory activity - Yuan Gao; Ying-Xiao Xiao; Hao Xu; Xue-Feng Wu; Yi-Lin Li; Hyun-Sun Lee; Long Cui (Phytochemistry Letters, 2025)

Hydrophobic agglomeration of different types of collectors in the separation of fine tenorite from quartz - Qiurong Long; Qiang He; Weiyong Cui; Yangge Zhu (Minerals Engineering, 2025)

The nitrogen migration investigation during the pyrolysis and oxidation of C3 amines - Zhi-Hao Zheng; Du Wang; Long Zhao; Jiu-Zhong Yang; Zhan-Dong Wang; Cui-Ping Wang; Zhen-Yu Tian (Fuel, 2025)

Integrated multi-omics dissection unveils transcriptional and miRNA-mediated regulation of amino acid biosynthesis networks during bud-to-bloom transition in Hemerocallis citrina - Xiao-Ke Li; Jin-Long Cui; Xue-Mei Qin (Food Bioscience, 2025)

Integrating HS-SPME-GCMS with chemometrics for identifying adulterated flaxseed oils and tracing origins of additives - Yan-Jin Wen; Long-He Wang; Meng Zhai; Hui Ma; Hua-Peng Cui; Lu Han; Guo-Bi Chai; Yi Lv; Qing-Xia Zheng; Yong-Jie Yu; Yuan-bin She (Food Control, 2025)

Grass carp reovirus VP6 inhibits IFN production by degrading TBK1 through the autophagy pathway - Xiao Xu; Zhuo-Cong Li; Bao-Jie Cui; Can Zhang; Na Xu; Yang-Yang Wang; Dan-Dan Chen; Long-Feng Lu; Shun Li (Fish & Shellfish Immunology, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Electricity-driven microbial production of medium-chain fatty acids from biowaste: From mechanisms to applications - Jiayu Gu; Zihan Cui; Yang Wu; Jing Sun; Xiong Zheng; Min Long; Yinguang Chen (Chemical Engineering Journal, 2025)

Competitive ion driven reversible Cu and Ni electrodeposition for smart windows with synergistic optical and thermal regulation - Wenhao Wang; Long Wang; Gu Liu; Lijun Yang; Tonghao Liu; Yina Cui; Lixuan Zhang; Qingyi Kang; Xu Tang; Lele Ma; Jinwen Ren; Xinyu Zhu; et al. (Chemical Engineering Journal, 2025)

Genetic influence of the brain on epigenetic age acceleration: evidence of a large‐scale genetic correlation study - Chengcheng Li; Jiaze Tang; Junshuan Cui; Niya Long; Wu Cen; Qibo Wu; Ming Yang; Liangzhao Chu; Xingwang Zhou (Biogerontology, 2025)

Comparative evaluation of selected adjuvants for possible application of Aeromonas caviae inactivated vaccine in crucian carp (Carassius auratus) - Han Lu; Tao-luo Tao; Yu-Long Liu; Fan Jia; Yi-feng Cui; Xiao-feng Shan (Aquaculture International, 2025)

Can environmental system reform enhance firms’ export product quality? Evidence from the environmental vertical reform in China’s prefecture-level cities - Yan Jiang; Long Tang; Xiaotian Wei; Cui Huang (Environment, Development and Sustainability, 2025)

Mechanisms of groundwater recovery and land subsidence mitigation in a piedmont plain - Long Zhao; Xiao-Wei Jiang; Yu-Mei Li; Yong Luo; Kun-Chao Lei; Wen-Jie Kou; Fang Tian; Miao-Zhuang Tian; Te Sha; Shu-Fang Wang; Wen-Jun Cui (Journal of Hydrology, 2025)

Visualization study on the effects of water addition on microscopic and macroscopic spray characteristics of methanol with high-pressure direct injection - Qianming Wang; Wuqiang Long; Wei Sang; Guangjie Jin; Zechuan Cui; Ge Xiao; Hua Tian; Jiangping Tian; Yang Wang (Fuel, 2025)

Alleviating moxifloxacin-induced biological inhibition in ethanol and Cl− coexisted wastewater: Why UV/H2O2 is better than Fenton - Yingying Zhang; Min Yang; Wenbo Cui; Lin-Ji Xu; Depeng Zhang; Yu Tao; Jing-Long Han; Aijie Wang (Chemical Engineering Journal, 2025)

Efficient methane decomposition to produce hydrogen and microwave absorption material by iron and nitrogen Co-doped Biocarbon: Synergistic mechanisms and performance - Haipeng Cui; Song Hu; Tao Yang; Limo He; Kai Xu; Long Jiang; Sheng Su; Yi Wang; Jun Xu; Jun Xiang (Biomass and Bioenergy, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Impact of the environmental endocrine disruptor flutamide on cryptorchidism: Molecular mechanisms involving connexin-43 and p38-MAPK signaling - Yu Zhou; Yifan Hong; Shengwen Wang; Luna He; Yan Cui; Yinghua Wu; Fuli Yan; Chunlan Long; Jing Gao (Reproductive Toxicology, 2025)

A machine learning-assisted electrochemical nanosensor based on bimetal-codoped MOF composites for simultaneous detection and removal of multiple fluoroquinolone antibiotics - Suisui He; Jiaheng Zhang; Junlin He; Zhonghui Luo; Wen Chen; Huimin Tang; Jiaqi Long; Jun Wang; Hua Wei; Cui-Yun Yu (Journal of Cleaner Production, 2025)

Effects of jets interaction and injection strategy on the combustion characteristics in TJI-HPDI methanol engine - Peng Wang; Wuqiang Long; Wentao Zhao; Mingfei Lu; Pengbo Dong; Hua Tian; JingChen Cui; Ge Xiao; Yang Wang; Jianlin Cao (Fuel, 2025)

High-sensitivity detection of hydrogen sulfide and water content using a Triphenylamine-based fluorescent probe: Applications in food safety monitoring - Yanqing Xu; Zhaojiang Yin; Qian Long; Haotian Xie; Xinying Yan; Fusheng Liao; Hanfeng Cui; Hao Fan (Food Chemistry, 2025)

Visual screening of Toxigenic Alternaria Fungi in citrus using CRISPR/Cas12a and quantum dot - Lu Yang; Chenxi Guo; Tian Zhang; Jiyao Dong; Lanrui Ma; Xiaoping Ma; Longyingzi Xie; Xinqi Long; Yongliang Cui; Yaohai Zhang; Yue He (Food Control, 2025)

Cyprinid herpesvirus 2 (CyHV-2) ORF67 inhibits IFN expression by competitively obstructing STING phosphorylation - Bao-Jie Cui; Can Zhang; Chu-Jing Zhou; Zhuo-Cong Li; Xiao Xu; Yang-Yang Wang; Dan-Dan Chen; Li Zhou; Long-Feng Lu; Shun Li (Fish & Shellfish Immunology, 2025)

Seismic performance of a post-earthquake repair-free bolted beam-to-column joint with slab - Xue-Chun Liu; Wen-Bin Cui; Xuesen Chen; Long-Xin Guo (Engineering Structures, 2025)

Development of an Ellipsoid Based Chart Datum Around the China Seas - Yanguang Fu; Yanxiong Liu; Mehdi Khaki; Fukai Peng; Xiaolong Mi; Yikai Feng; Xiaoli Deng; Long Yang; Qinghua Tang; Li Cui (Marine Geodesy, 2025)

Electric vehicle range prediction considering real-time driving factors and battery capacity index - Xinwei Ma; Jiaao Li; Hongjun Cui; Long Cheng; Yanjie Ji; Jianbiao Wang (Transportation Research Part D: Transport and Environment, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

3D printing programmed diagnostic and therapeutic bioactive “all-in-one” microspheres with multistimuli responsiveness for cartilage regeneration - Feifei Zhou; Wenjing Zhang; Yuan Yang; Shuyu Liu; Jing Long; Siqi Zhang; Jiaming Cui; Yuxiao Lai; Weimin Zhu (Chemical Engineering Journal, 2025)

High performance piezoelectric nanogenerator based on aligned single crystal BaTiO3 nanowires for self-powered applications - Minglei Li; Zheng Li; Sobia Yaseen; Nuanyang Cui; Peixian Li; Jing Sun; Jinmei Liu; Xiaozhou Lü; Long Gu (Chemical Engineering Journal, 2025)

Double-punch strategy: Macrophage membrane-enveloped imipramine and aCD47 reprograms tumor microenvironment to enhance glioblastoma immunotherapy - Long Zhang; Yining Zhang; Ji Qi; Jiahao Yu; Haojie Hu; Xiangrong Lu; Jiangpeng Fan; Guimei Cui; Rutong Yu; Xiuping Zhou (Chemical Engineering Journal, 2025)

Comparative study of maternal behaviours and reproductive performance among three Minpig hybrid breeds - Xuankai Huang; Lei Zhang; Shengyue Gao; Yan Song; Li Wang; Shengwei Di; Long Jin; Hongbao Wang; Shiquan Cui; Xibiao Wang (Applied Animal Behaviour Science, 2025)

Microbiome and metabolome alterations in calves with enterohemorrhagic Escherichia coli and dyspeptic diarrhea - Lantian Huang; Zhengyu Lin; Xinyi Zhu; Long Guo; Luying Cui; Junsheng Dong; Kangjun Liu; Jianji Li; Heng Wang (Veterinary Microbiology, 2025)

Assembly and co-occurrence pattern of microbial communities in bulk and rhizosphere soils of Pinus elliottii plantations on sandy lands in China - Haozhi Long; Si-Yi Xiong; Yang-Mei Mo; Bei-Bei Zeng; Bin-Xuan Shan; Ting Xiao; Yang Gao; Chaoyu Cui (Plant and Soil, 2025)

Interspecific differences in nitrogen form acquisition strategies contribute to species dominance - Ming Guan; Xiao‐Cui Pan; Jian‐Kun Sun; Ji‐Xin Chen; Xiao‐Lin Wei; Bernhard Schmid; Michel Loreau; Yu‐Long Feng (Ecology, 2025)
Plant's ability to use prevalent or less prevalent soil nitrogen (N) forms may affect their dominance within vegetation types, and these partitioning‐driven changes in dominance may facilitate species co‐existence. However, the mechanisms underlying these processes remain unclear, particularly given the strong influence of altitude on soil N forms, which in turn affect plant N acquisition strategy. In this study, we first determined the effects of preference and plasticity in N form uptake on partitioning of soil N forms and species dominance, and then assessed the relative importance of these two N form use strategies for 19 dominant and non‐dominant species in three vegetation types along an altitudinal gradient on Changbai Mountain, northeast China. To achieve this, we measured dominance, the contents of different N forms in rhizosphere soils, their proportional contributions to leaf N, and N form uptake preference and plasticity for these 19 species. Our results show significant interspecific differences in the proportional contributions of different soil N forms to leaf N within all three vegetation types, providing a novel mechanism underlying niche differentiation among plants. Species dominance was positively associated with the proportional contributions of soil dissolved organic N (the most prevalent N form) and the main inorganic N form to leaf N, while negatively with that of the subordinate inorganic N. These associations were not altered by the altitude‐driven changes in the absolute and proportional contents of different soil N forms, suggesting a potentially widespread phenomenon. Both preference and plasticity in N form uptake contributed to the proportional contributions of different N forms to leaf N, and therefore to species dominance and co‐existence within vegetation types. Furthermore, N form preference was more critical for non‐dominant relative to dominant species and at high relative to low altitude, while N form uptake plasticity was more important for dominant species and at low altitude. Our study provides robust evidence for the interspecific niche differentiation in N form uptake, contributing to species dominance and co‐existence within vegetation types, and reveals the mechanisms (plasticity and preference) underlying the association between species dominance and the uptakes of different N forms.

Glycosidase inhibitory isoflavones from the seeds of Cullen corylifolium and their structure–activity relationship study - Ying-Xiao Xiao; Yi-Ran Jiang; Wen-Hui Xu; Yuan Gao; Tian-Tian Bei; Hao Xu; Xue-Feng Wu; Hyun-Sun Lee; Long Cui (Natural Product Research, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

Preparation and characterization of a monoclonal antibody against MCP of largemouth bass ranavirus and investigation of the virus's tissue tropism - Yuhui Wang; Yaoda Wang; Tianmei Hu; Hongye Cui; Long Huang; Haiyue Chen; Baozhou Wu; Shuguang Hao; Wenlong Cai; Yali Wu; Jiping Zhang; Weiwei Zeng (Aquaculture, 2025)

From complex networks to urban heat island governance: Structural analysis and intervention in xiamen island's heat island network - Huanjia Cui; Yu Wang; Qiang Yu; Jikai Zhao; Weijie Sun; Xinyu Yang; Bowen Chi; Ji Long; Buyanbaatar Avirmed (Sustainable Cities and Society, 2025)

Synergistic effects of heat stress and mastitis induced by K. pneumoniae on inflammation responses and blood-milk barrier in rats - Jia Guo; Qinqin Cao; Zhihao Wang; Pengzi Wang; Kangjun Liu; Long Guo; Junsheng Dong; Luying Cui; Jianji Li; Guoqiang Zhu; Xia Meng; Heng Wang (Journal of Thermal Biology, 2025)

Ammonia-methanol laminar combustion experiment and chemical kinetic modeling within broad range of ambient pressure - Mingfei Lu; Wuqiang Long; Zechuan Cui; Pengbo Dong; Lixin Cong; Fuxing Wei; Qingyang Wang; Peng Wang; Dongsheng Dong; Hua Tian (Fuel, 2025)

Integrating photocatalytic hydrogen evolution with antibiotic degradation over a dual Z-scheme heterojunction - Churu Zhang; Shuai Hu; Weigang Cui; Shuangjiang Li; Long Tian; Xinggen Yuan; Waseem Tariq; Kaili Yao; Yunfei Zhi; Tianding Hu; Shaoyun Shan (Chemical Engineering Journal, 2025)

Waterproofing enhancement mechanism of the double sealing gaskets: Experimental test and theoretical analysis - Hua-Yong Li; Huai-Na Wu; Dong-Lin Feng; Lei Liu; Qing-long Cui; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Deep learning–based data anomaly detection for highway slope structural health monitoring: A comparative study - Shi Dong; Zhiyou Long; Shiyuan Zhang; Jianwei Wang; Chen Zuo; Chao Yang; Jinyi Jiang; Zhiwei Cui; Zhaolong Wan (Transportation Geotechnics, 2025)

N-acetylglucosamine sensor, Ngs1 contributes to Beauveria bassiana vegetative growth, oxidative phosphorylation, fungal development, and cell wall integrity during entomopathogen-insect interaction - Zhou Cui; Wu-Wei-Jie Yang; Zhi-Hao Yang; Long-Bin Zhang; Yi Guan (Pesticide Biochemistry and Physiology, 2025)

High-resolution spatio-temporal estimation of street-level air pollution using mobile monitoring and machine learning - Qi Long; Jun Ma; Cui Guo; Mingzhu Wang; Qian Wang (Journal of Environmental Management, 2025)

Evolution characteristics of microwave absorbing carbon material on surface of CoFe2O4@biochar during hydrogen production from methane decomposition process - Haipeng Cui; Song Hu; Tao Yang; Limo He; Kai Xu; Long Jiang; Sheng Su; Yi Wang; Jun Xu; Jun Xiang (Fuel, 2025)

CSWin-MBConv: A dual-network fusing CNN and Transformer for weed recognition - Jinrong Cui; Youliu Zhang; Hao Chen; Yaoxuan Zhang; Hao Cai; Yu Jiang; Ruijun Ma; Long Qi (European Journal of Agronomy, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Exploring the Correlation Between Varied Serum Iodine Nutritional Levels and Anti-Thyroglobulin Antibodies - Qiuyi Song; Tingting Xu; Yu Wang; Hongyan Wei; Feng Tan; Yanting Chen; Fang Fang; Tingkai Cui; Ziyun Pan; Xiaohui Guo; Wen Chen; Jun Shen; et al. (Biological Trace Element Research, 2025)

Fe2+ inhibits spring viraemia of carp virus proliferation via ATG14-dependent autophagy - Zhuo-Cong Li; Can Zhang; Na Xu; Xiao Xu; Ke-Jia Han; Chu-Jing Zhou; Yang-Yang Wang; Bao-Jie Cui; Dan-Dan Chen; Long-Feng Lu; Shun Li (Aquaculture, 2025)

Precision water recharge facilitates spikelet development and seed growth in Carex schmidtii: Implications for near-natural restoration of degraded semi-arid wetlands - Mingye Zhang; Shuchen Liu; Guodong Wang; Yu An; Ming Jiang; Dongjie Zhang; Geng Cui; Long Yan; Shouzheng Tong (Journal of Environmental Management, 2025)

Phosphorus speciation in the hyporheic zone and its response to sediment-water quality-biological activity coupling effect - Yue Qu; Jinxi Song; Yongqing Long; Nan Li; Songzhe Fu; Bin Tang; Qihao Tao; Qifan Cui; Ken Qin (Journal of Environmental Management, 2025)

Homogeneous-pore-creation in pitch-based carbon fibers by extraction-activation and their application as supports for catalytic hydrogenation - Shuo Li; Hexin Jiang; Xiangyi Long; Marcos Millan; Tiantian Li; Zhengwei Cui; Guanming Yuan (Fuel, 2025)

Differential impact of wildfire and rice straw ash on the skin microbiota of Rana dybowskii adults and tadpoles - Xin-zhou Long; Ming-da Xu; Wen-jing Dong; Xiu-mei Yang; Li-yong Cui; Qing Tong (Environmental Pollution, 2025)

Mantle induced hydration and oxidation of intracontinental granite sources in the North China Craton - Chuan-Mao Yang; Yi-Gang Xu; Xiao-Ping Xia; Jin-Hui Yang; Xiao-Long Huang; Christopher J. Spencer; Jin-Feng Sun; Ze-Xian Cui; Meng-Jing Li; Wan-Feng Zhang; Qing Yang (Earth and Planetary Science Letters, 2025)

Influence of wildfire ash concentration on development, survival, and skin and gut microbiota of Rana dybowskii - Qing Tong; Ming-da Xu; Wen-jing Dong; Xin-zhou Long; Xiao-yun Han; Li-yong Cui (Science of The Total Environment, 2025)

Life cycle environmental and economic assessment of Phosphogypsum utilization in China - Lu Chen; Xiaoyu Luan; Feng Han; Yuwei Zhao; Huiying Yang; Long Zhang; Yongquan Yin; Wei Liu; Zhaojie Cui (Resources, Conservation and Recycling, 2025)

Microplastics distribution, transport and potential risks in sediments across different functional areas of megacities: From storm sewer networks to urban river - Yan Wu; Cui Zhou; Xingjian Long; Luyue Zhang; Jinhui Chen; Xingyu Gao; Jing Zhang; Qingguo Wang (Journal of Water Process Engineering, 2025)

Design method of simplified dynamic test model for high-rise building with underground structures considering nonlinear behavior similarity - Rui Wang; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Yao-Zhong Cui; Han Zhang; Jia-Long Li (Engineering Structures, 2025)

Activation of 5-HT6 Receptors in the Ventrolateral Orbital Cortex Produces Anti-Anxiodepressive Effects in a Rat Model of Neuropathic Pain - Yu-Long Zhao; Hui-Yuan Yi; Sani Sa’idu Baba; Yi-Xiao Guo; Xiao-Cui Yuan; Xue-Mei Hou; Ling-Li Liang; Fu-Quan Huo (Molecular Neurobiology, 2025)

Intelligent cooperative control for flexible landing on small celestial bodies - Pingyuan Cui; Dongyue Zhao; Zelong Chen; Dantong Ge; Jiateng Long (Advances in Space Research, 2025)

Retrieval of total suspended matter concentration in the yellow river estuary offshore area based on QAA-RF model - Lianwei Li; Zhi Zheng; Cunjin Xue; Long Cui; Shiyu Wu; Yu Wang (International Journal of Remote Sensing, 2024)

Formation and evolution of thermokarst landslides in the Qinghai-Tibet Plateau, China - Tao Wei; Hao Wang; Peng Cui; Yan Wang; Bo Zhang; Rui-Long Wei; Zhen-Xing Liu; Chao-Yue Li (Science of The Total Environment, 2024)

Calcium homeostasis imbalance mediates DEHP induced mitochondrial damage in cerebellum and the antagonistic effect of lycopene - Jia-Gen Cui; Hao Zhang; Ming-Shan Chen; Jia-Xin Wang; Yi Zhao; Jin-Long Li (Science of The Total Environment, 2024)

Shifting agricultural land use and its unintended water consumption in the North China Plain - Liang Dong; Di Long; Caijin Zhang; Yingjie Cui; Yanhong Cui; Yiming Wang; Luoqi Li; Zhongkun Hong; Ling Yao; Jinling Quan; Liangliang Bai; Hao Wang; et al. (Science Bulletin, 2024)

Efficient isolation of rhamnolipids from fermentation broth via an advanced acid-induced precipitation process with heat treatment - Li Luo; Mingda Guo; Deyu Zhang; Yang Hu; Tianyou Cui; Mengqian Zhao; Jian Yin; Xuwei Long (Food and Bioproducts Processing, 2024)

Understanding the synergistic catalysis of balanced Cu0-Cu+ sites and oxygen vacancies in Cu/ZrO2 catalysts for the efficient hydrogenation of furfural - Xinling Yang; Zhou Chen; Jingjing Tan; Yuanna Zhang; Jinglei Cui; Changzhen Wang; Li Fang; Yulei Zhu; Long Huang; Hu Shi; Yongzhao Wang (Chemical Engineering Journal, 2024)

An improved method for identifying the genotypic sex in Rana dybowskii - Long Jin; Hanyu Liu; Xinshuai Jiang; Zhiheng Du; Yaguang Tian; Xuankai Huang; Yuan Xu; Shiquan Cui (Conservation Genetics Resources, 2024)

First report of Fusarium nirenbergiae causing leaf blight on Dichondra repens in China - Yuxin Zhao; Keyun Zhang; Yaru Li; Haozhi Long; Chaoyu Cui (Journal of Plant Pathology, 2024)

Effect of alfalfa downy mildew (Peronospora aestivalis) infection on the growth and development of Therioaphis trifolii (Homoptera: Aphidiidae) - Lin-bo Xu; Liang-bin Yu; Fang-zheng Yue; Dan-yang Wang; Wen-long Li; Ba-teer Wulan; Yan-wei Cui (Crop Protection, 2024)

Dynamics of phytoplankton assemblages determined by the HPLC–PIGMENTUM approach and the related environmental variables in the northern Chinese sea - Long Yang; Zhengguo Cui; Jian Zhang; Hongwei Wang; Hanbai Wang; Di Zhang; Xiaokun Ding; Daojun Zha; Li Gao; Tao Jiang (Marine Pollution Bulletin, 2024)

What influences intermodal Choices: Metro-Centric, Bus-Centric, Hybrid? insights from Machine learning Approaches - Xinwei Ma; Xiaolin Tian; Hongjun Cui; Mingjia He; Jianbiao Wang; Long Cheng (Transportation Research Part D: Transport and Environment, 2024)

Effect of connection modes on seismic responses of a diaphragm wall-subway station system subjected to mainshock-aftershock sequences - Long-Ji Zhang; Zhen-Dong Cui (Soil Dynamics and Earthquake Engineering, 2024)

Heavy metal migration and enrichment in desulfurization wastewater during low-temperature triple effect evaporation process - Xiangzheng Cui; Zhikang Wang; Rihong Xiao; Kaiyan Long; Zhuo Xiong; Yongchun Zhao; Junying Zhang (Journal of Cleaner Production, 2024)

Self-adhesive, mechanically strong, and conductive organogel for flexible/wearable electronics and underwater electronic skin - Zhaowei Cui; Bing Jiang; Xinhuan Dai; Zihao Guo; Jianan Niu; Zilong Dong; Yong Long; Weiguo Hu (Chemical Engineering Journal, 2024)

Chitin nanocrystal Pickering emulsions for sustainable release pesticide microencapsulation with superior leaf adhesion and enhanced safety - Long Chen; Liang Li; Hongyan Chen; Bo Cui; Fei Gao; Jinming Gao; Xiang Zhao; Yan Wang; Haixin Cui; Zhanghua Zeng (Chemical Engineering Journal, 2024)

Biodegradable MAM-based amphiphilic block copolymers: Toward efficient and eco-friendly kinetic inhibitors for methane hydrate formation - Li Wan; Xiang-Long Ding; Ai-Xiang Liu; Hao Cui; Jin-Rong Zhong; Yi-Min Dai (Chemical Engineering Journal, 2024)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

Annual variations in characteristics and sources analysis of VOCs during the ozone season in the Taiyuan Basin, China, from 2020 to 2022 - Zhentao Wang; Tengfei Long; Yang Cui; Qiusheng He; Jun Wang; Shaolong Gao; Xinming Wang (Air Quality, Atmosphere & Health, 2024)

Morphology and Effect of Load on Bridge Piers Impacted by Continuous Sea Ice - Li Gong; Yue Cui; Yunfei Du; Long Qin; Xinyuan Zhao (Journal of Marine Science and Engineering, 2024)
In order to study the collision of sea ice on bridge piers of a sea-crossing bridge, this study establishes a finite element model of the impact of sea ice on bridge piers in aqueous media based on explicit dynamics analysis software and programming software using the arbitrary Lagrangian Eulerian (ALE) method. The results show that, when the sea-ice spacing is larger than the sea-ice edge length, the increase in sea-ice spacing leads to a decrease in the collision force and a significant increase in the probability of climbing and overturning. The increase in sea-ice mass significantly increases the impact force on the bridge abutment, and the peak value increases linearly with the increase in mass, and the sea-ice climbing and overturning phenomena are obvious. Different shapes of sea ice are obtained by cutting the sea-ice field with the two-dimensional Voronoi method, and the maximum impact force increases significantly with the increase in the average area. Irregularly shaped sea ice leads to a larger impact force and triggers the accumulation climbing phenomenon, which is verified by experiments, and the experimental values are in good agreement with the simulated values. In conclusion, this study reveals the significant effects of the spacing, mass, and shape of sea ice on the impact force of bridge piers, which provides an important reference for the design of bridge structures.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Ru0.7Cu0.3/W18O49 Schottky junction for visible-light-driven hydrogen generation from ammonia borane hydrolysis - Shu-Bin Li; Wei-Yang Long; Chuan-Qi Li; Yan-Xin Duan; Rong-Chao Cui; Zhong-Yi Liu; Xin-Zheng Yue (Fuel, 2024)

Current status of molecular rice breeding for durable and broad-spectrum resistance to major diseases and insect pests - Xiaoyan Cheng; Guohua Zhou; Wei Chen; Lin Tan; Qishi Long; Fusheng Cui; Lei Tan; Guoxing Zou; Yong Tan (Theoretical and Applied Genetics, 2024)
In the past century, there have been great achievements in identifying resistance ( R ) genes and quantitative trait loci (QTLs) as well as revealing the corresponding molecular mechanisms for resistance in rice to major diseases and insect pests. The introgression of R genes to develop resistant rice cultivars has become the most effective and eco-friendly method to control pathogens/insects at present. However, little attention has been paid to durable and broad-spectrum resistance, which determines the real applicability of R genes. Here, we summarize all the R genes and QTLs conferring durable and broad-spectrum resistance in rice to fungal blast, bacterial leaf blight (BLB), and the brown planthopper (BPH) in molecular breeding. We discuss the molecular mechanisms and feasible methods of improving durable and broad-spectrum resistance to blast, BLB, and BPH. We will particularly focus on pyramiding multiple R genes or QTLs as the most useful method to improve durability and broaden the disease/insect spectrum in practical breeding regardless of its uncertainty. We believe that this review provides useful information for scientists and breeders in rice breeding for multiple stress resistance in the future.

Influence of scion cultivar on the rhizosphere microbiome and root exudates of Phaseolus vulgaris in grafting system - Xiuli Wei; Yuanyuan Cui; Jiaqi Wang; Guoyuan Song; Ying Cao; Long Liu; Zhixin Liu; Jing Yang; Chen Li; Jiao Wang; Moran Li; Xiao Xiao (Plant and Soil, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

A gap filling method for daily evapotranspiration of global flux data sets based on deep learning - Long Qian; Lifeng Wu; Zhitao Zhang; Junliang Fan; Xingjiao Yu; Xiaogang Liu; Qiliang Yang; Yaokui Cui (Journal of Hydrology, 2024)

Improving high uncertainty of evapotranspiration products under extreme climatic conditions based on deep learning and ERA5 reanalysis data - Long Qian; Xingjiao Yu; Lifeng Wu; Zhitao Zhang; Shuailong Fan; Ruiqi Du; Xiaogang Liu; Qiliang Yang; Rangjian Qiu; Yaokui Cui; Guomin Huang; Yicheng Wang (Journal of Hydrology, 2024)

A human-skin inspired self-healing, anti-bacterial and high performance triboelectric nanogenerator for self-powered multifunctional electronic skin - Jinmei Liu; Jiongyao Xu; Yuxin Wang; Zheng Li; Minglei Li; Nuanyang Cui; Fangfang Zhao; Leixin Meng; Long Gu (Chemical Engineering Journal, 2024)

Chemistry in phase change energy storage: Properties regulation on organic phase change materials by covalent bond modification - Long Geng; Jipeng Cui; Changle Zhang; Yabo Yan; Jiateng Zhao; Changhui Liu (Chemical Engineering Journal, 2024)

Spatial downscaling of GRACE-derived groundwater storage changes across diverse climates and human interventions with Random Forests - Yiming Wang; Chen Li; Yingjie Cui; Yanhong Cui; Yuancheng Xu; Tejasvi Hora; Esha Zaveri; Aude-Sophie Rodella; Liangliang Bai; Di Long (Journal of Hydrology, 2024)

Impact of wildfire ash on skin and gut microbiomes and survival of Rana dybowskii - Ming-da Xu; Wen-jing Dong; Xin-zhou Long; Xue-wen Yang; Xiao-yun Han; Li-yong Cui; Qing Tong (Journal of Hazardous Materials, 2024)

Deciphering the therapeutic efficacy of FGF19 and FGF21 in NAFLD: A comparative genomic and metabolic analysis - Lengyun Wei; Pengpeng Long; Xianlong Ye; Shenglong Zhu; Siyuan Cui (Food Bioscience, 2024)

Efficient gaseous mercury removal by nano-amorphous red selenium and recycling design of HgSe nanoparticles - Kaiyan Long; Rihong Xiao; Tianle Zhang; Xiangzheng Cui; Zhuo Xiong; Yongchun Zhao; Junying Zhang (Chemical Engineering Journal, 2024)

Remarkably enhanced acidic photoelectrochemical glycerol oxidation achieving the theoretical maximum photocurrent of BiVO4 through anion modulation - Jun-Yuan Cui; Tian-Tian Li; Zhao-Hua Yin; Long Chen; Jian-Jun Wang (Chemical Engineering Journal, 2024)

Identification of key genes involved in lignin and flavonoid accumulation during Tilia tuan seed maturation - Lei Liu; Cui Long; Xuri Hao; Rui Zhang; Chenqi Li; Yuepeng Song (Plant Cell Reports, 2024)

Analysis of negative skin friction and bending moment on batter rock-socketed pile - Yu-xiao Ren; Yaxin Li; Wenxi Cui; Wei Guo; Daokun Zhuang; Saiyue Cui; Long Zhang (Marine Georesources & Geotechnology, 2024)

Impact of antibiotic therapy on cutaneous and gut microbiota in Rana dybowskii amphibians: Insights and implications - Xin-zhou Long; Wen-jing Dong; Ming-da Xu; Xue-dong Han; Xiao-yun Han; Li-yong Cui; Qing Tong (Aquaculture, 2024)

Height estimation of sugarcane tip cutting position based on multimodal alignment and depth image fusion - Chunming Wen; Bingxu Hou; Jianheng Li; Wanling Wu; Yunzhi Yan; Wenxuan Cui; Youzong Huang; Xiaozhu Long; Hongliang Nong; Yuchun Lu (Biosystems Engineering, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

H*ads dynamics engineering via bimetallic Pd–Cu@MXene catalyst for enhanced electrocatalytic hydrodechlorination - Lan-Ying Liu; Min-Hua Cui; John Justo Ambuchi; Shi-Ming Niu; Xin-Hui Li; Wo-Long Wang; He Liu; Guo-Shuai Liu; Ai-Jie Wang (Environmental Research, 2024)

Direct and efficient catalytic conversion of biomass-derived 2-methyltetrahydrofuran to 1,3-pentadiene via acid-base coupling of lanthanum phosphate - Ruilin Feng; Yanlong Qi; Long Cui; Chenxi Bai (Chemical Engineering Journal, 2024)

Natural resource development, economic policy uncertainty and urban residents’ consumption in China: a nonlinear ARDL and time-varying parameter vector autoregressive with stochastic volatility approach - Tianxiang Long; Xiangying Cui; Jiale Yan; Cem Işık; Stefania Pinzon; Muhammad Irfan (Stochastic Environmental Research and Risk Assessment, 2024)
Increased risks of economic policy uncertainty and overexploitation of natural resources exist in China. At the same time, the growth rate of urban residents’ consumption has generally declined. The paper analyses the role of economic policy uncertainty (EPU) and natural resource exploitation on the urban residents’ consumption in China. Based on the data from the first quarter of 2002 to the third quarter of 2021, the paper uses a nonlinear autoregressive distributed lag model to verify the asymmetric effects. Then the paper constructs a time-varying parameter vector autoregressive model with stochastic volatility term to analyze the nonlinear responses. Impulse response analysis was used to further explain the relationship between the three. The negative impact of rising EPU on urban residents’ consumption is larger than its reduction. Negative shocks to natural resource development increase the urban residents’ consumption. Positive shocks reduce the urban residents’ consumption. There is a time-varying non-linear effect of EPU and natural resource development on urban residents’ consumption in China. The negative impact of EPU on urban consumption has been further exacerbated by major crises such as the financial crisis, COVID-19 and the post-crisis period. The negative impact of natural resource development diminished after the government introduced industrial upgrading policies and environmental regulations. This study provides constructive suggestions for the optimization of economic policies and the improvement of urban consumption. This study also enriches consumer theory and provides new evidence for the resource curse hypothesis.

Amphidiploid production of a distant hybrid Populus simonii × P. euphratica cv. ‘Xiaohuyang-1’ and resulting in phenotypic variation - Ying Zhang; Zi-Yu Wang; Xiao-Tong Cui; Xiao-Xiao Zhang; Jin-Wang Zhang; Long Tie; Jun Wang (New Forests, 2024)

Paleosalinity reconstruction in offshore lacustrine basins based on elemental geochemistry: a case study of Middle-Upper Eocene Shahejie Formation, Zhanhua Sag, Bohai Bay Basin - Long Sun; Shenghe Wu; Dali Yue; Wenfu Cui (Journal of Oceanology and Limnology, 2024)

Comparative transcriptomic and epigenomic analyses to identify the cold resistance-associated genes and disclose the regulatory mechanisms in tilapias - Guili Song; Ran Liu; Shaoxiong Chen; Qing Li; Zongbin Cui; Yong Long (Aquaculture, 2024)

Five new meroterpenes from the seeds of Psoralea corylifolia and their diacylglycerol acyltransferase activity - Xiao-Jing Shao; Meng-Xue Xiu; Xue-Hui Wang; Wen-Hui Xu; Ying-Xiao Xiao; Yuan Gao; Yi-Ran Jiang; Tian-Tian Bei; Hyun-Sun Lee; Long Cui (Phytochemistry Letters, 2024)

Evaluation and determinants of metro users' regularity: Insights from transit one-card data - Xinwei Ma; Xiaolin Tian; Zejin Jin; Hongjun Cui; Yanjie Ji; Long Cheng (Journal of Transport Geography, 2024)

Engineering a transport pathway to boost extracellular production of human lactoferrin in Komagataella phaffii - Lingrui Wang; Yangyang Li; Shixiu Cui; Xianhao Xu; Yanfeng Liu; Jianghua Li; Guocheng Du; Xueqin Lv; Long Liu (Food Bioscience, 2024)

Nutritional- and flavor-enhancing effects of biomass production by Rhodotorula spp. on cantaloupe juice - Ruitong Hou; Shuyu Liu; Na Lv; Baozhong Cui; Yongxue Wei; Feiyang Long; Hongfei Fu; Yunyang Wang (Food Bioscience, 2024)

Sugarcane borers: species, distribution, damage and management options - Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Yong Zhao; Cui-Xian Qin; Miao Wang; You-Qiang Pan; Shao-Long Wei; Dong-Liang Huang (Journal of Pest Science, 2024)
Lepidopteran borers stand out as the most destructive pests in sugarcane, leading to reductions in stalk weight, juice quality and sugar recovery. Presently, integrated pest management (IPM) systems are utilized for sugarcane borer management, employing diverse methods encompassing cropping system, chemical pesticides, behavioral manipulation, biological agents and the selection of resistant varieties. However, the effectiveness of this strategy remains controversial due to concerns about harmful residues, formulation limitations, environmental variability, labor shortages and increased input costs. Currently, multiple lines of transgenic sugarcane expressing insecticidal genes from the bacterium Bacillus thuringiensis (Bt) have been developed globally, offering the prospect of increases production with reduced pesticides application, thereby eliminating the negative effect of IPM. In Brazil, the first genetically modified sugarcane cultivars resistant to the sugarcane borer have been approved and released for commercial cultivation, shedding a bright light on a viable solution for sugarcane borers. This paper reviews borer species and distribution, the significant damage caused by sugarcane borers, current control approaches and the future effective control strategies. Additionally, this work provides comprehensive understanding on Bt sugarcane, serving as an additional tool to complement conventional sugarcane borers control resistance programs.

Formation of environmentally persistent free radicals and their risks for human health: a review - Xueying Wang; Haijiao Liu; Yonggang Xue; Long Cui; Long Chen; Kin-fai Ho; Yu Huang (Environmental Chemistry Letters, 2024)

An improved multi-filter fusion indoor localization algorithm based on INS and UWB - Long Cheng; Chen Cui; Zhijian Zhao; Yuanyuan Shi (Earth Science Informatics, 2024)

The Effect of Selenium on Endometrial Repair in Goats with Endometritis at High Cortisol Levels - Hanqing Li; Changning Yuan; Heng Wang; Luying Cui; Kangjun Liu; Long Guo; Jianji Li; Junsheng Dong (Biological Trace Element Research, 2024)

Application and Comparison of Different Regression Models in Iodine Balance Experiment on Women of Childbearing Age and Pregnant Women - Yu Wang; Xiaoxiao Tian; Qiuyi Song; Wenqiang Wang; Xiaohui Guo; Tingkai Cui; Ziyun Pan; Yongjie Chen; Wen Chen; Long Tan; Wanqi Zhang (Biological Trace Element Research, 2024)

Rice straw ash and amphibian health: A deep dive into microbiota changes and potential ecological consequences - Wen-jing Dong; Ming-da Xu; Xue-wen Yang; Xiu-mei Yang; Xin-zhou Long; Xiao-yun Han; Li-yong Cui; Qing Tong (Science of The Total Environment, 2024)

Imaging gastrointestinal damage due to acute mercury poisoning using a mitochondria-targeted dual near-infrared fluorescent probe - Jianjian Zhou; Jianchun Li; Xiaotong Xu; Shi Long; Ningning Cui; Yong Zhang; Lihong Shi; Jin Zhou (Journal of Hazardous Materials, 2024)

Synergistic catalysis of TiO2/WO3 photoanode and Sb–SnO2 electrode with highly efficient ClO• generation for urine treatment - Changhui Zhou; Pengbo Wang; Jinhua Li; Yan Zhang; Jing Bai; Hanbo Cui; Geying Liu; Mingce Long; Baoxue Zhou (Journal of Hazardous Materials, 2024)

Advances in the preparation, characterization, and biological functions of chitosan oligosaccharide derivatives: A review - Bing Li; Jingchun Cui; Tiantian Xu; Yunshu Xu; Mingxin Long; Jiaqi Li; Mingzhi Liu; Ting Yang; Yuguang Du; Qingsong Xu (Carbohydrate Polymers, 2024)

Di (2-ethylhexyl) phthalate induced lipophagy-related renal ferroptosis in quail (Coturnix japonica) - Yu Zhu; Xiang-Yu Ma; Ling-Ge Cui; Ya-Ru Xu; Chen-Xi Li; Milton Talukder; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Efficient removal of Congo Red by carbonized Ganoderma lucidum spore with Fe3O4 - Jueyu Wang; Yue Yang; Long Bai; Yongqi Wang; Daizong Cui; Na Zhao; Min Zhao (Journal of Water Process Engineering, 2024)

Heteroatom substitution enhances generation and reactivity of surface-activated peroxydisulfate complexes for catalytic fenton-like reactions - Yan Wei; Jie Miao; Jiahao Cui; Junyu Lang; Qunli Rao; Baoxue Zhou; Mingce Long; Pedro J.J. Alvarez (Journal of Hazardous Materials, 2024)

Selecting essential factors for predicting reference crop evapotranspiration through tree-based machine learning and Bayesian optimization - Long Zhao; Yuhang Wang; Yi Shi; Xinbo Zhao; Ningbo Cui; Shuo Zhang (Theoretical and Applied Climatology, 2024)

Spatial and temporal distribution characteristics and risk assessment of heavy metals in groundwater of Pingshuo mining area - Long Sun; Tingxi Liu; Limin Duan; Xin Tong; Wenrui Zhang; He Cui; Zhiting Wang; Guofeng Zheng (Environmental Geochemistry and Health, 2024)

A ratiometric fluorescent indicator-displacement assay for on-site determination and intracellular imaging of nitroxinil - Cui-Zhen Lu; Cai-Yun Wang; Chao Song; Tianyi Qin; Taoyuze Lv; Conghui Zeng; Shihong Chen; Zhongyong Xu; Zhiqing Xun; Bin Liu; Ya-Long Wang; Ming-Qiang Zhu (Food Chemistry, 2024)

pH-responsive multi-network composite cellulose-based hydrogels for stable delivery of oral IgY-Fab fragments - Minquan Xia; Zhaoyu Cui; Tao Zeng; LiZhi Lu; Long Sheng; Zhaoxia Cai (Food Chemistry, 2024)

Enhancing safety through the biodegradable pesticide microcapsules produced via melt emulsification and interfacial polymerization - Long Chen; Weiqun Zhang; Huan Du; Xiquan Ding; Liang Li; Hongyan Chen; Fei Gao; Bo Cui; Jinming Gao; Haixin Cui; Yishan Yao; Zhanghua Zeng (Chemical Engineering Journal, 2024)

Spatial soil heterogeneity rather than the invasion of Spartina alterniflora drives soil bacterial community assembly in an Eastern Chinese intertidal zone along an estuary coastline - Yukai Zhang; Mo Li; Jiao zhang; Jun Cui; Xinyi Wang; Miaomiao Song; Qicheng Qiao; Xi-En Long (CATENA, 2024)

Spatiotemporal reconstruction of global ocean surface pCO2 based on optimized random forest - Huisheng Wu; Lejie Wang; Xiaochun Ling; Long Cui; Ruixue Sun; Na Jiang (Science of The Total Environment, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

Unveiling lake ice phenology in Central Asia under climate change with MODIS data and a two-step classification approach - Yuancheng Xu; Di Long; Xingdong Li; Yiming Wang; Fanyu Zhao; Yanhong Cui (Remote Sensing of Environment, 2024)

Efficient catalytic oxidation of VOCs by a Pd-Pt/SiO2 catalyst: The cooperative catalysis of dual metal sites - Jinglei Cui; Yujun Cui; Jingjing Tan; Huirong Zhang; Mengyuan Gu; Long Huang (Journal of Environmental Chemical Engineering, 2024)

Petroleum-like fuels with substantially enriched branched iso-paraffins and benzenes via boehmite-assisted pyrolysis of oil shale - Guojing Xu; Zhaoyang Ren; Zhenpeng Wang; Lijie Cui; Jian-Zheng Su; Xiang-Long Meng; Penglei Chen; Peng Li; Nannan Wang; Xiang Hao; Bo Guan (Fuel, 2024)

Shaking table test and numerical simulation of a precast frame-shear wall structure with innovative untopped precast concrete floors - Rui Pang; Yuan-yuan Sun; Zhu Xu; Ke Xu; Jing Cui; Long-ji Dang (Engineering Structures, 2024)

Efficient preparation and isolation of sophorolipids with excellent pH-regulated water solubility via environmentally friendly acid-induced chemical modifications - Yang Hu; Tianyou Cui; Zhihong Yang; Lu Ren; Li Luo; Mengqian Zhao; Mingjie Jin; Xuwei Long (Chemical Engineering Journal, 2024)

Eocene lacustrine microbialites in the western Qaidam Basin, China: implication for the sedimentary record and hydrocarbon potential - Xiang Li; Jiangong Wang; Guohui Long; Li Xu; Jun Cui; Xiujian Sun; Yuling Wang (Carbonates and Evaporites, 2024)

Assessing the Interactive Effects of High Salinity and Stocking Density on the Growth and Stress Physiology of the Pacific White Shrimp Litopenaeus vannamei - Fei Liu; Jinfeng Sun; Jinnan Long; Lichao Sun; Chang Liu; Xiaofan Wang; Long Zhang; Pengyuan Hao; Zhongkai Wang; Yanting Cui; Renjie Wang; Yuquan Li (Fishes, 2024)
This study was conducted to evaluate the effects of high salinity combined with stocking density on Litopenaeus vannamei. Three salinity gradients, namely, 28 g/L, 36 g/L, and 44 g/L, and two stocking densities, namely, 300 and 600 shrimp/m3, were used to analyze the synergistic effect of high salinity and stocking density on the growth performance, digestibility, and energy budgets of L. vannamei. The experimental testing period lasted 45 days. The research results showed that a salinity level of 36 g/L was the most suitable salinity level for shrimp growth under both high and low stocking densities. The body weight, specific growth rate, and relative weight gain of the shrimp in the 36 g/L salinity group were significantly higher than those in the other two salinity groups under both high and low stocking densities. The high-density farming group with 600 shrimp/m3 exhibited a significant inhibition of shrimp growth compared to the low-density group under the same salinity conditions. The activities of amylase, lipase, and protease in the high-density-group shrimp gradually decreased with an increase in salinity, and the three digestive enzymes had the same overall effect of changing trends. This indicates that under high-density farming conditions, the increase in salinity is not conducive to the digestive function of shrimps. At the same time, the proportion of respiratory energy to feeding energy gradually decreased in the high-density group and with the increase in salinity. However, under the same salinity conditions, the higher the stocking density, the higher the energy consumed by respiration compared to the low-density group. In addition, the expression of the growth-related gene’s small nuclear ribonucleoprotein polypeptide G (SNRPG) under high stocking density was significantly lower than that in the low-density group at a salinity of 28 g/L, and ribosomal protein L7 (RPL7) expression was also significantly lower under high stocking density than that in the low-density group at a salinity of 44 g/L. The expression levels of molting-related genes retinoid X receptor (RXR), ecdysone receptor (ECR), and ecdysone-induced protein 75 (E75) were significantly higher in the 36 g/L salinity group compared with the other two salinity groups under high-stocking-density treatment. The findings indicate that the synergistic effects of salinity and stocking density have a significant impact on the growth of L. vannamei, and excessive salinity would inhibit its growth in the process of high-density culturing.

Critical Roles of Surface-Enhanced Heterogeneous Oxidation of SO2 in Haze Chemistry: Review of Extended Pathways for Complex Air Pollution - Zihao Zhang; Haiwei Li; Wingkei Ho; Long Cui; Qihui Men; Li Cao; Yunjiang Zhang; Junfeng Wang; Cheng Huang; Shun-cheng Lee; Yu Huang; Mindong Chen; et al. (Current Pollution Reports, 2024)

Recent advance in high-intensity ultrasound modification of blue food protein: Mechanisms, functional properties and structural alterations - Zhihui Yu; Yating Gao; Xinyi Jia; Shuai Cui; Li Ma; Dan Zheng; Xin Li; Long Li; Lixin Zhang; Yisheng Chen (Trends in Food Science & Technology, 2024)

Whole-body aging mediates the association between exposure to volatile organic compounds and osteoarthritis among U.S. middle-to-old-aged adults - Hao-long Zhou; Dong-sheng Di; Zhang-bo Cui; Ting-ting Zhou; Ting-ting Yuan; Qian Liu; Jian-li Zhang; Xiao Luo; Dan-yang Ling; Qi Wang (Science of The Total Environment, 2024)

Characteristic chromanone acids from Calophyllum membranaceum: Determination of C-3 configuration and anti-inflammatory activity - Wei Shen; Lun Li; Qing-He Liu; Jia-Min Cui; Wei Shi; Xin-Hong Shi; Xiao-Qi Zhang; Wen-Cai Ye; Xiao-Long Hu; Hao Wang (Phytochemistry, 2024)

Overexpression of PtoMYB99 diminishes poplar tolerance to osmotic stress by suppressing ABA and JA biosynthesis - Tao Long; Fengming Yang; Zihao Chen; Yuhang Xing; Xia Tang; Banglan Chen; Wenli Cui; Lucas Gutierrez Rodriguez; Lijun Wang; Yongfeng Gao; Yinan Yao (Journal of Plant Physiology, 2024)

Experimental study of the ignition chamber with accelerating cavity applying to methanol lean combustion - Fuxing Wei; Qianming Wang; Jianlin Cao; Zechuan Cui; Wuqiang Long; Hua Tian; Jiangping Tian; Dongsheng Dong; Yang Wang (Fuel, 2024)

Thermo-responsive liposome nano-vesicles for co-delivery of emamectin benzoate and nitenpyram with synergistic pest control - Qian Du; Xi-Quan Ding; Fei Gao; Bo Cui; Ting-Yu Wang; Fang-Yuan Chen; Long Chen; Hong-Yan Chen; Hai-Xin Cui; Yan Wang; Zhang-Hua Zeng (Chemical Engineering Journal, 2024)

Subduction of the Paleo Pacific Plate at the southeast edge of the South China Block during the Early to Middle Jurassic: Sedimentary records from Fujian Province - Long Leng; Zhongjie Xu; Kunning Cui; Shiyao Gao; Ningchen Sun (Island Arc, 2024)
During the Mesozoic, the tectonic evolution of the southeastern margin of the South China Block was mainly influenced by the subduction of the Palaeo‐Pacific Plate. The sedimentary basins along the southeastern margin of the South China Block have preserved the sedimentary record of this process. In this paper, the sedimentary rocks of the Lishan Formation and Zhangping Formation in the Zhangping area of the southeastern margin of the South China Block are studied in terms of sedimentology, petrography, lithogeochemistry, U–Pb chronology of detrital zircon, and zircon trace elements. The study shows that the detrital zircon U–Pb age of the Lishan Formation is 2965–202 Ma, with two major age groups: 253–220 Ma and 1925–1799 Ma; the detrital zircon U–Pb age of the Zhangping Formation is 2587–190 Ma, with two major age groups: 246–234 Ma and 1929–1861 Ma; the ancient sediments in the samples are affected by recycle, and the Early Jurassic source area in the study area is an acidic magma zone, while the Middle Jurassic source area is located in a moderately acidic magma zone and recycle body; the Early Jurassic Lishan Formation and Middle Jurassic Zhangping Formation are mainly derived from the Wuyi Massif. In the upper section of the Lishan Formation, the secondary age groups of ca.448 and ca.773 Ma occur, and the detrital zircons in this section are mainly from the Jiangnan orogenic belt. The ongoing subduction of the Paleo‐Pacific Plate led to the formation of diverse back‐arc basins within the region; during the Early Jurassic, it was a back‐arc compressional basin, transitioning into a back‐arc extensional basin during the Middle Jurassic.

Offshore aquaculture in China - Lina Long; Huang Liu; Mingchao Cui; Chenglin Zhang; Chong Liu (Reviews in Aquaculture, 2024)
The mariculture industry is planning to move offshore due to the decline of China's inshore fishery resources, the deterioration of the water environment, inefficient industrial structure and other influencing factors. This article first analyses the imbalance between supply and demand of aquatic products, the development space of offshore aquaculture and the supporting policies, thereby concluding that China has significant potential to develop offshore aquaculture. Subsequently, the development status of offshore aquaculture in China is examined. The research progress of China's offshore aquaculture facilities, marine hydrology, environmental carrying capacity, aquaculture technology and the status of aquaculture operation equipment are also summarized. Furthermore, the problems existing in the development of offshore aquaculture are pointed out. On this basis, future development ideas for China's offshore aquaculture can be planned in terms of sea area layout, optimized and improved seed production systems, and research and development of offshore aquaculture technology and pellet feed. The relationship between the development of offshore aquaculture and ecological protection should be coordinated. Additionally, an energy security system can be built based on clean energy, and the development of related industries can be driven through the complementary industrial division of labour. The present work aims to provide a reference for promoting the development of offshore aquaculture in China.

A method for estimating particulate organic carbon at the sea surface based on geodetector and machine learning - Huisheng Wu; Long Cui; Lejie Wang; Ruixue Sun; Zhi Zheng (Frontiers in Marine Science, 2023)
Particulate organic carbon (POC) is an essential component of the carbon pump within marine organisms. Exploring estimation methods for POC holds substantial significance for understanding the marine carbon cycle. In this study, we investigated the spatial heterogeneity of 30 factors and POC concentrations using geodetector to account for nonlinearity, diversity, and complexity. Ultimately, 20 factors including sea surface temperature, sea surface salinity, and chlorophyll-a were selected as modeling variables. Six machine learning models—backpropagation neural network, convolutional neural network, attention-based neural network, random forest (RF), adaptive boosting, and extreme gradient boosting were used to compare their performance. The results indicate that among the six machine learning algorithms, RF exhibits the strongest performance, with a root mean square error of 0.11 [log(mg/m 3 )] and an average percentage deviation of 2.73%. Global annual average sea surface POC concentrations were estimated for 2007 and compared to NASA’s POC product. The outcomes indicate that the RF model-based estimation method displays enhanced accuracy in estimating POC concentrations within intricate coastal environments, while the backpropagation neural network performed better in estimating POC concentrations in open ocean areas. Leveraging the RF model, global sea surface POC concentrations were estimated for the years 2007 through 2016, enabling a spatiotemporal analysis. The analysis unveils heightened POC concentrations in coastal regions and lower levels in open ocean areas. Furthermore, POC concentrations were greater in high-latitude regions compared to mid and low latitude counterparts. In conclusion, the global sea surface POC product in this study exhibits heightened spatial resolution and improved data completeness in contrast to other products. It enhances the accuracy of conventional POC estimation methods, particularly within coastal regions.

First report of Globisporangium ultimum causing postharvest fruit rot of peach in China - Long Zeng; Hailin Xia; Chaoyu Cui (Journal of Plant Pathology, 2023)

Seismic behavior of subway station in the soft clay field before and after freeze-thaw cycle - Zhen-Dong Cui; Long-Ji Zhang; Chen-Yu Hou (Soil Dynamics and Earthquake Engineering, 2023)

Does environmental regulation improve firms' export product quality? Empirical evidence based on China's key regional air pollution and control policy - Yan Jiang; Long Tang; Cui Huang (Journal of Cleaner Production, 2023)

Allyl methyl disulfide (AMDS) prevents N,N-dimethyl formamide-induced liver damage by suppressing oxidative stress and NLRP3 inflammasome activation - Long-Xia Li; Lin Wang; Shuo Wang; Xiu-Ning Zhang; Hong Liu; Yan-Jing Zhang; Chuan-Tao Wu; Cui-Li Zhang; Tao Zeng (Food and Chemical Toxicology, 2023)

Correction to: Genome‑wide identification of NRAMP family genes in Populus trichocarpa and their roles in transport of heavy metals - Siqin Liu; Tao Long; Zihao Chen; Jikai Liu; Wenli Cui; Haiqin Leng; Yuhang Xing; Lucas Gutierrez Rodriguez; Yongfeng Gao; Yinan Yao (Tree Genetics & Genomes, 2023)

Genome-wide identification of NRAMP family genes in Populus trichocarpa and their roles in transport of heavy metals - Siqin Liu; Tao Long; Zihao Chen; Jikai Liu; Wenli Cui; Haiqin Leng; Yuhang Xing; Lucas Gutierrez Rodriguez; Yongfeng Gao; Yinan Yao (Tree Genetics & Genomes, 2023)

Prediction of Rice Yield Based on Multi-Source Data and Hybrid LSSVM Algorithms in China - Long Zhao; Shunhao Qing; Fei Wang; Hui Wang; Hao Ma; Yi Shi; Ningbo Cui (International Journal of Plant Production, 2023)

Investigation of ammonia cracking combined with lean-burn operation for zero-carbon combustion and NO/N2O/NO2 improvements - Xiangyu Meng; Meichao Qin; Lizi Liu; Zechuan Cui; Jiangping Tian; Wuqiang Long; Mingshu Bi (Journal of Cleaner Production, 2023)

Efficient production of biosurfactant surfactin by a newly isolated Bacillus subtilis (sp.) 50499 strain from oil-contaminated soil - Yulu Du; Yue Wang; Tianyou Cui; Lianpeng Ge; Fan Yu; Mengqian Zhao; Qihang Xu; Mingjie Jin; Bo Chen; Xuwei Long (Food and Bioproducts Processing, 2023)

Fabrication of a disposable aptasensing chip for simultaneous label-free detection of four common coexisting mycotoxins - Jing Qian; Yue Liu; Haining Cui; Huiyuan Yang; Mustafa Hussain; Kun Wang; Jie Wei; Lingliang Long; Lijun Ding; Chengquan Wang (Analytica Chimica Acta, 2023)

Elemental sulfur-driven autotrophic denitrification process for effective removal of nitrate in mariculture wastewater: Performance, kinetics and microbial community - Lu Wang; Jun Liu; Yongfu Li; Zhihao Liu; Long Zhang; Hong Che; Hongwu Cui; Ying Zhang (Chemosphere, 2023)

Bioactive ellagitannins and phenylpropanoid glycosides from the seed of Torreya grandis - Xue-Hui Wang; Xiao-Jing Shao; Yi-Ran Jiang; Tian-Tian Bei; Wen-Hui Xu; Bo-Wen Ren; Hyun-Sun Lee; Long Cui (Phytochemistry Letters, 2023)

Environmental occurrence, risk, and removal strategies of pyrazolones: A critical review - Yanqing Zhang; Jingyuan Wang; Hanlin Cui; Shuhong Gao; Long Ye; Zhiling Li; Shichen Nie; Jinglong Han; Aijie Wang; Bin Liang (Journal of Hazardous Materials, 2023)

1H NMR-based metabolomics combined with chemometrics to detect edible oil adulteration in huajiao (Zanthoxylum bungeanum Maxim.) - Chuanjian Cui; Mingyue Xia; Jianglin Chen; Biwen Shi; Chuanyi Peng; Huimei Cai; Long Jin; Ruyan Hou (Food Chemistry, 2023)

Synergetic modulation on solvation structure and electrode interface to achieve lithium-ion batteries cycled at ultra-low temperature - Jixu Yang; Kecheng Long; Ziyang Guo; Yunlong Cui; Canhui Ling; Zhibin Wu; Feixiang Wu; Weifeng Wei; Yuejiao Chen; Xiaobo Ji; Lin Mei; Libao Chen (Chemical Engineering Journal, 2023)

Evaluation and analysis of green efficiency of China's coastal ports under the "double carbon" goal: two improved DEA models with CO2 emissions - Linlin Cui; Long Chen; Xiao Yang (Environment, Development and Sustainability, 2023)

Biodegradability enhancement of waste lubricating oil regeneration wastewater using electrocoagulation pretreatment - Li-li Shan; Zhao Tan; Yu Chen; Ruo-shan Wang; Meng Zhang; Chang-long Pang; Yu-Hong Cui; Zhi-min Liao; Hong-qiang Ma; Ze-bing Zhu (Environmental Science and Pollution Research, 2023)

The role of BECCS technology in achieving carbon neutrality: evidences from China’ coal power sector - Yun-Long Zhang; Jia-Ning Kang; Min Dai; Juan-Juan Hou; Lan-Cui Liu; Yi-Ming Wei; Hua Liao (Environment, Development and Sustainability, 2023)

Real-time missing seedling counting in paddy fields based on lightweight network and tracking-by-detection algorithm - Jinrong Cui; Hong Zheng; Zhiwei Zeng; Yuling Yang; Ruijun Ma; Yuyuan Tian; Jianwei Tan; Xiao Feng; Long Qi (Computers and Electronics in Agriculture, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Design of atomic cobalt selenide-doped sulfurized polyacrylonitrile cathode with enhanced electrochemical kinetics for high performance lithium-SPAN batteries - Zhi-Qiang Xu; Rong Zou; Wen-Wu Liu; Guang-Long Liu; Yun-Shou Cui; Yi-Xiao Lei; Ya-Wen Zheng; Wen-Jun Niu; You-Zhi Wu; Bing-Ni Gu; Ming-Jin Liu; Fen Ran; et al. (Chemical Engineering Journal, 2023)

Equivalent seismic behaviors of artificial frozen-thawed soft clay with a new reduction factor of shear stress - Zhen-Dong Cui; Long-Ji Zhang; Chen-Yu Hou (Cold Regions Science and Technology, 2023)

Numerical simulation of freezing temperature field and frost heave deformation for deep foundation pit by AGF - Zhen-Dong Cui; Long-Ji Zhang; Chong Xu (Cold Regions Science and Technology, 2023)

An advanced treatment process for 3-high wastewater discharged from crude oil storage tanks - Xue-Wen Li; Zhong-Yi Cui; Bao-Fu Zhao; Jin-An Wang; Yue-Qin Song; Xiao-Long Zhou (Environmental Science and Pollution Research, 2023)

The composition characteristics of endophytic communities and their relationship with metabolites profile in Ephedra sinica under wild and cultivated conditions - Hui Zhang; Ye Xia; Jin-Long Cui; Xin Ji; Shuang-Man Miao; Gang Zhang; Yi-Min Li (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Pyrroloquinoline quinone promotes growth and intestinal health and alleviates tris(1,3-dichloro-2-propyl) phosphate-induced hepatic oxidative stress in zebrafish - Chao-Qun Li; Yong-Jun Cao; Long-Fei Cui; Chun-Yang Zhang; Bei-Li Zhang; Qin-Yuan Ma (Aquaculture, 2023)

Seismic response analysis of shallowly buried subway station in inhomogeneous clay site - Zhen-Dong Cui; Long-Ji Zhang; Zhi-Xiang Zhan (Soil Dynamics and Earthquake Engineering, 2023)

Variable drivers of surface turbulence under condition of stratified density currents in a tributary bay of Three Gorges Reservoir - Lianghong Long; Hui Xu; Meng Yan; Xia Yang; Xingxing Zhao; Daobin Ji; Yujie Cui; Zhongyong Yang; Defu Liu; Zhengjian Yang (Journal of Hydrology, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Three new sesquilignans from the stems of Eleutherococcus senticosus and their bioactivities - Yue Zhang; Yi-Ming Zhao; Xiao-Jing Shao; Xue-Hui Wang; Tian-Tian Bei; Yi-Ran Jiang; Wen-Hui Xu; Hyun-Sun Lee; Meng-Xue Xiu; Jian Song; Long Cui (Phytochemistry Letters, 2023)

Simultaneously achieving enhanced water adsorption and rapid adsorbed hydroxyl transfer toward MXene-based materials for highly efficient alkaline electrocatalytic hydrogen evolution - Yang Meng; Ping Zeng; Xiao-Yu Yang; Zhan Liu; Xiao-Yun Li; Cui-Fang Ye; Yu Li; Jin-Ping Liu; Bao-Lian Su; Li-Hua Chen; Yi-Long Wang (Chemical Engineering Journal, 2023)

Toward a better understanding of uncertainty for satellite precipitation products over complex terrain with sparse rain gauge data - Yingying Gai; Xunjian Long; Zhihao Wei; Xinxin Sui; Bo Jiang; Xi Chen; Dingfeng Yu; Shengguang Qin; Yaokui Cui (Atmospheric Research, 2023)

Concurrent dominant pathways of multifunctional products formed from nocturnal isoprene oxidation - Haiwei Li; Long Cui; Yu Huang; Yunjiang Zhang; Junfeng Wang; Mindong Chen; Xinlei Ge (Chemosphere, 2023)

The N6-methyladenosine binding proteins YTH03/05/10 coordinately regulate rice plant height - Long Cai; Song Cui; Tao Jin; Xiaolong Huang; Haigang Hou; Benyuan Hao; Zhuang Xu; Liang Cai; Yuan Hu; Xue Yang; Lei Zhou; Ting Yu; et al. (Plant Science, 2023)

Disturbance and restoration of soil microbial communities after in-situ thermal desorption in a chlorinated hydrocarbon contaminated site - Jiali Shentu; Qianqian Chen; Yuxue Cui; Yangyang Wang; Li Lu; Yuyang Long; Min Zhu (Journal of Hazardous Materials, 2023)

Visualization study on the effects of pre-chamber jet ignition and methane addition on the combustion characteristics of ammonia/air mixtures - Xiaolei Zhang; Jiangping Tian; Zechuan Cui; Siyuan Xiong; Shuo Yin; Quan Wang; Wuqiang Long (Fuel, 2023)

Thermal stable poly-dioxolane based electrolytes via a robust crosslinked network for dendrite-free solid-state li-metal batteries - Jie Cui; Yunfei Du; Long Zhao; Xiaocheng Li; Zixu Sun; Dong Li; Hao Li (Chemical Engineering Journal, 2023)

Azospirillum Aestuarii sp. nov., a Novel Nitrogen-Fixting and Aerobic Denitrifying Bacteria Isolated from an Estuary of a Freshwater River - Can-Hai Xu; Gen Chen; Yan Liu; Wei Xiao; Xiao-Long Cui; Zhang-Gui Ding; Wei-Hong Liu; Yong-Xia Wang (Current Microbiology, 2023)

Deployment optimization of battery swapping stations accounting for taxis’ dynamic energy demand - Tian-yu Zhang; En-jian Yao; Yang Yang; Long Pan; Cui-ping Li; Bin Li; Feng Zhao (Transportation Research Part D: Transport and Environment, 2023)

Root exudation processes induce the utilization of microbial-derived components by rhizoplane microbiota under conservation agriculture - Yüze Li; Mei Long; Yuting Hou; Wei Li; Xiaoliang Qin; Baogang Zhang; Tao Wen; Yongxing Cui; Ziting Wang; Yuncheng Liao (Soil Biology and Biochemistry, 2023)

iTRAQ-based proteomic analysis reveals the underlying mechanism of postmortem tenderization of refrigerated porcine Longissimus thoracis et lumborum muscle - Long Xu; Yueshan He; Xiaoyu Yuan; Kelin Liu; Yue Cui; Hanjun Ma; Changming Ma; Xiaoling Yu (Meat Science, 2023)

Superhydrophobic aerogel blanket with magnetic and solar heating effect enables efficient continuous cleanup of highly viscous crude oil - Xueyan Wang; Xianfeng Liu; Zhong Liu; Wenying Cui; Shilong Gao; Jun Zhang; Tingting Fan; Seeram Ramakrishna; Yun-Ze Long (Journal of Hazardous Materials, 2023)

Visualization study on combustion characteristics of direct-injected hydrous methanol ignited by diesel in a constant volume combustion chamber - Qianming Wang; Fuxing Wei; Pengbo Dong; Ge Xiao; Zechuan Cui; Jiangping Tian; Xiuyong Shi; Wuqiang Long (Fuel, 2023)

1H NMR-based metabolomic approach combined with machine learning algorithm to distinguish the geographic origin of huajiao (Zanthoxylum bungeanum Maxim.) - Chuanjian Cui; Mingyue Xia; Ziqi Wei; Jianglin Chen; Chuanyi Peng; Huimei Cai; Long Jin; Ruyan Hou (Food Control, 2023)

Application of logistic regression model for hazard assessment of landslides caused by the 2012 Yiliang Ms 5.7 earthquake in Yunnan Province, China - Jia-le Jin; Yu-long Cui; Chong Xu; Jun Zheng; Hai-bo Miao (Journal of Mountain Science, 2023)

Superpixel segmentation integrated feature subset selection for wetland classification over Yellow River Delta - Long Cui; Jiahua Zhang; Zhenjiang Wu; Lan Xun; Xiaopeng Wang; Shichao Zhang; Yun Bai; Sha Zhang; Shanshan Yang; Qi Liu (Environmental Science and Pollution Research, 2023)

Membrane-based nanoconfined heterogeneous catalysis for water purification: A critical review✰ - Quang Viet Ly; Lele Cui; Muhammad Bilal Asif; Waris Khan; Long D Nghiem; Yuhoon Hwang; Zhenghua Zhang (Water Research, 2023)

Improved thermal insulation and compressive property of bimodal poly (lactic acid)/cellulose nanocomposite foams - Qian Ren; Wanwan Li; Shijie Cui; Wenyu Ma; Xiuyu Zhu; Minghui Wu; Long Wang; Wenge Zheng; Takeshi Semba; Masahiro Ohshima (Carbohydrate Polymers, 2023)

Prediction Model for Reference Crop Evapotranspiration Based on the Back-propagation Algorithm with Limited Factors - Long Zhao; Liwen Xing; Yuhang Wang; Ningbo Cui; Hanmi Zhou; Yi Shi; Sudan Chen; Xinbo Zhao; Zhe Li (Water Resources Management, 2023)

Self-weight consolidation process of water-saturated deltas on Mars and Earth - Mingjie Zhang; Qi Yan; Yi Xu; Long Xiao; Jiannan Zhao; Dingbao Song; Jiang Wang; Shuoran Yu; Zhenkun He; Hansheng Liu; Deshan Cui; Xiaoping Zhang (Icarus, 2023)

Quantification of the asynchronous gas diffusivity in macro-/micropores using a Nelder-Mead simplex algorithm and its application on predicting desorption-based indexes - Wei Zhao; Kai Wang; Yang Ju; Long Fan; Heng Cao; Yun Yang; Longyong Shu; Zhongkai Feng; Ran Cui; Xiaofang Guo; Liuyi Wang (Fuel, 2023)

Discrimination of the harvesting season of green tea by alcohol/salt-based aqueous two-phase systems combined with chemometric analysis - Xiao-Hua Zhang; Hui-Na Cui; Jing-Jing Zheng; Xiang-Dong Qing; Kai-Long Yang; Ya-Qian Zhang; Lu-Meng Ren; Le-Yuan Pan; Xiao-Li Yin (Food Research International, 2023)

Understanding of combustion characteristics and NO generation process with pure ammonia in the pre-chamber jet-induced ignition system - Xiangyu Meng; Chenhan Zhao; Zechuan Cui; Xiaolei Zhang; Mingkun Zhang; Jiangping Tian; Wuqiang Long; Mingshu Bi (Fuel, 2023)

Heme-oxygenase-1 as a target for phthalate-induced cardiomyocytes ferroptosis - Jia-Xin Wang; Yi Zhao; Ming-Shan Chen; Hao Zhang; Jia-Gen Cui; Jin-Long Li (Environmental Pollution, 2023)

The reaction mechanism of highly dispersed Cu atoms and ultrafine MnOx nanoclusters co-modified ZSM-5 based on in-situ heteronuclear substitution for catalytic oxidation C6H14 - Jian Li; Jingnan Hu; Yingjie Shi; Jiajia Zhao; Hongchang Wang; Shuang Deng; Yutao Cui; Fan Wang; Hongyan Long; Yuling Tan (Chemical Engineering Journal, 2023)

Effects of South-to-North Water Diversion Project on groundwater and land subsidence in Beijing, China - Kunchao Lei; Fengshan Ma; Beibei Chen; Yong Luo; Wenjun Cui; Long Zhao; Xinhui Wang; Aihua Sun (Bulletin of Engineering Geology and the Environment, 2023)

How Do Gene Expression Patterns Change in Response to Osmotic Stresses in Kuruma Shrimp (Marsupenaeus japonicus)? - Yuquan Li; Zhihao Zhang; Zhongkai Wang; Zhitong Deng; Ruiyang Zhao; Jinfeng Sun; Pengyuan Hao; Long Zhang; Xiaofan Wang; Fei Liu; Renjie Wang; Yanting Cui (Journal of Marine Science and Engineering, 2022)
Euryhaline crustaceans cope with external salinity changes by mechanisms of osmoregulation. In the current study, we first cloned and confirmed the ORF sequences of the ion-transportation-related genes Na+/K+-ATPase α subunit (NKAα), cytoplasmic carbonic anhydrase (CAc), and V-type H+-ATPase G subunit (VHA-G), and water channels of aquaporins (AQP3, AQP4, and AQP11) from kuruma shrimp (Marsupenaeus japonicus). Further tissue expression patterns showed a higher expression of MjAQP4, MjCAc, MjNKAα, and MjVHA-G in the gills, as well as a higher expression of MjAQP3 and MjAQP11 in the intestine and muscle, respectively. Then, qPCR analysis was used to assess the mRNA expression levels of those osmoregulatory genes in both post-larvae and adult shrimp when they were exposed to acute salinity stress or salinity acclimation. The results revealed significantly decreased expression levels of MjAQP3, MjAQP11, MjNKAα, and MjCAc, and higher expression levels of MjAQP4 and MjVHA-G when the post-larvae shrimp were directly subjected to 10‰ or 50‰ salinity. Moreover, similar expression patterns were also observed in the post-larvae shrimp during the accommodation to 10‰ or 50‰ salinity. As to the adult shrimp, significantly higher expression levels of those genes were observed in the gills after exposure to 10‰ salinity, whereas only the expression levels of MjAQP3, MjAQP11, and MjNKAα were up-regulated in the gills at 40‰ salinity. In contrast, the expression of MjVHA-G was significantly decreased at 40‰ salinity. Finally, during the acclimation to 10‰ salinity, the expression levels of MjAQP3, MjAQP11, and MjNKAα were also significantly elevated, while the expression of MjCAc was significantly decreased in the gills. In addition, the expression levels of MjAQP3, MjAQP4, MjCAc, and MjVHA-G were significantly decreased in the gills during the acclimation to 55‰ salinity. The findings of the study suggest that the examined genes are critical for the adaptation of aquatic crustaceans to changing environmental salinity. Our study lays as the foundation for further research on osmoregulation mechanisms in M. japonicus.

Silencing circ_0074371 inhibits the progression of sepsis-induced acute kidney injury by regulating miR-330-5p/ELK1 axis - Qiu-yuan Wang; Rong-rong Zhang; Long Cui; Ya-ping Sun (Mammalian Genome, 2022)

The R2R3-MYB gene CgMYB4 is involved in the regulation of cell differentiation and fiber development in the stamens of Chelone glabra L. - Chunlan Piao; Zhenrui Gao; Siming Yuan; Feifei Li; Min-Long Cui (Protoplasma, 2022)

EEG microstate temporal Dynamics Predict depressive symptoms in College Students - Xiaorong Qin; Jingyi Xiong; Ruifang Cui; Guimin Zou; Changquan Long; Xu Lei (Brain Topography, 2022)

Correction to: Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Landslides triggered by the 1970 Ms 7.7 Tonghai earthquake in Yunnan, China: an inventory, distribution characteristics, and tectonic significance - Yu-long Cui; Jun-hong Hu; Chong Xu; Hai-bo Miao; Jun Zheng (Journal of Mountain Science, 2022)

Spatial distribution of saline (salinization) frozen soil in the Qinghai-Tibet Engineering Corridor - Shanshan Zhang; Hui Peng; Yuanhong Dong; Xiaosa Yuan; Long Jin; Yunhu Shang; Fuqing Cui (Arabian Journal of Geosciences, 2022)

Geological risks and countermeasures for mountain tunneling through a large karst cave in Southwest Hubei, China: a case study - Yan-Wei Li; Qing-Long Cui; Qiang Wu; Jie Sun (Arabian Journal of Geosciences, 2022)

Investigation on oxygen-controlled sewage sludge carbonization with low temperature: from thermal behavior to three-phase product properties - Fan Yu; Yanjun Hu; Lianming Li; Qianqian Guo; Yonghao Zhu; Long Jiao; Yihong Wang; Xiaoqiang Cui (Environmental Science and Pollution Research, 2022)

Flavonoid components and gene expression analysis reveal flower pigmentation difference between Magnolia biondii and its variety M. biondii var. purpurascens - Ning-hang Wang; Meng-yi Dai; Gang Zheng; Peng-jie Chang; Ling-juan Xuan; Zhi-gao Liu; Ya-ling Wang; Shao-yu Cheng; Zhuo-wei Wang; Hai-long Wang; Cui-hua Gu; Chao Zhang; et al. (Trees, 2022)

Early changes to the extracellular space in the hippocampus under simulated microgravity conditions - Yajuan Gao; Hongbin Han; Jichen Du; Qingyuan He; Yanxing Jia; Junhao Yan; Hui Dai; Bin Cui; Jing Yang; Xunbin Wei; Liu Yang; Rui Wang; et al. (Science China Life Sciences, 2022)

A method for calculating stabilizing pile spacing by integrating the mechanical characteristics of soil arching - Jianhui Long; Meiping Li; Lipeng Cui; Lingling Zhang; Jin Lu (Arabian Journal of Geosciences, 2022)

A study of the conversion of different evaporation pans in South China based on the extreme learning machine model - Long Qian; Lifeng Wu; Xiaogang Liu; Jianhua Dong; Sien Li; Qiliang Yang; Yaokui Cui (Hydrological Sciences Journal, 2021)

Correction to: AGGF1 protects from myocardial ischemia/reperfusion injury by regulating myocardial apoptosis and angiogenesis - Yu Liu; Hui Yang; Lina Song; Nan Li; Qiu-Yue Han; Cui Tian; Erhe Gao; Jie Du; Yun-Long Xia; Hui-Hua Li (Apoptosis, 2021)

Simulation and optimal control for a long‐distance water diversion project under different rainfall types: A case study in the Middle Route of China's South‐to‐North Water Diversion Project * - Yu Qiao; Jiahong Li; Wei Cui; Yan Long; Xiaohui Lei (Irrigation and Drainage, 2021)
Rainfall and rainstorms pose potential risks and significant threats to open‐channel water diversion projects. In long‐distance water diversion projects, it is difficult to observe the hydraulic response through measured data directly and comprehensively. Without accurate hydraulic responses and advanced control strategies for the different rainfall types, operators or decision‐makers are unable to respond effectively to hydraulic changes in the case of sudden occurrences of rainfall or rainstorms. In this study, a simulation and optimal control model focusing on solving the Saint Venant equation based on the computational finite difference method and the combined particle swarm optimization algorithm, was established and applied to a long‐distance water diversion project, namely the Middle Route of the South‐to‐North Water Diversion Project, China, to analyse the hydraulic response and control the disturbance of various rainfall types. The simulation model was validated based on the calculation results, indicating that the simulation model yielded a relatively high precision with an error margin of 2.5%. The optimal control model can effectively reduce the maximum increase in water level caused by the different rainfall types in the range of 0.10–0.20 m.

Dammarane-type saponins from Gynostemma pentaphyllum and their cytotoxicities - Wei-Ye Cui; Yulian Jin; Hui Liu; Ma-Li Zu; Xin-Fang Zhai; Ce Yang; Yu-Long Gu; Yong Cheng; Xiang-Lan Piao (Natural Product Research, 2021)

Observations on a magnetotactic bacteria-grazing ciliate in sediment from the intertidal zone of Huiquan Bay, China - Si Chen; Kaixuan Cui; Wenyan Zhang; Yicong Zhao; Tian Xiao; Hongmiao Pan; Wuchang Zhang; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Characterization and diversity of magnetotactic bacteria from sediments of Caroline Seamount in the Western Pacific Ocean - Kaixuan Cui; Wenyan Zhang; Jia Liu; Cong Xu; Yicong Zhao; Si Chen; Hongmiao Pan; Tian Xiao; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Comparison of the Bulk and Rhizosphere Soil Prokaryotic Communities Between Wild and Reintroduced Manglietiastrum sinicum Plants, a Threatened Species with Extremely Small Populations - Dai-Fa Su; Qing-Qing Shen; Jun-Yu Yang; Zhi-Ying Li; Wei Xiao; Yong-Xia Wang; Zhang-Gui Ding; Xiao-Long Cui (Current Microbiology, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

Shared and specific patterns of structural and functional thalamo-frontal disturbances in manic and euthymic pediatric bipolar disorder - Yi-Bing Guo; Wei-Jia Gao; Zhi-Liang Long; Wei-Fang Cao; Dong Cui; Yong-Xin Guo; Qing Jiao; Jian-Feng Qiu; Lin-Yan Su; Guang-Ming Lu (Brain Imaging and Behavior, 2021)
Bipolar disorder (BD) is clinically defined by alternating depressive and manic episodes with a separated period of euthymia. Thalamo-frontal loop plays vital role in psychotic symptoms, altered motor control and executive difficulties in BD. It remains unclear that structural and functional alterations of thalamo-frontal loop among the different mood states in BD, especially in pediatric BD(PBD). Twenty manic PBD (mPBD), 20 euthymic PBD (ePBD) and 19 healthy controls (HCs) were included in the study. By analyzing the T1 images and fMRI signals, thalamus volume and frontal grey matter cortical thickness were tested, and functional connectivity (FC) between bilateral thalamus and frontal cortex was calculated. Relationship between clinical indices and thalamo-frontal FC was also evaluated in mPBD and ePBD adolescents. Compared to HCs, the cortical thickness of left middle frontal gyrus (MFG), bilateral superior frontal gyrus (SFG) was significantly decreased in both mPBD and ePBD patients, and volume of left thalamus and cortical thickness of right MFG significantly decreased in mPBD patients. Compared to that of the HCs and ePBD subjects, thalamo-frontal hyperconnectivity with MFG was found in mPBD, and compared with that of HCs, thalamo-frontal hypoconnectivity with precentral gyrus/SFG was found in ePBD. In ePBD patients, episode times positively correlated with FC values between thalamus and precentral gyrus. The findings of the present study demonstrate detailed knowledge regarding shared and specific structural and functional disruption in thalamo-frontal loop in mPBD and ePBD subjects. Thalamo-frontal abnormalities reported in adult BD subjects were also observed in adolescent BD patients, and thalamo-frontal dysfunction may be a crucial treatment target in BD.

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

Analysis of the Cd(II) Adsorption Performance and Mechanisms by Soybean Root Biochar: Effect of Pyrolysis Temperatures - Qiuyue Wang; Peixin Cui; Qiang Yang; Long Chen; Weixuan Wang; Wangang Deng; Yujun Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

A catastrophic natural disaster chain of typhoon-rainstorm-landslide-barrier lake-flooding in Zhejiang Province, China - Yu-long Cui; Jun-hong Hu; Chong Xu; Jun Zheng; Jiang-bo Wei (Journal of Mountain Science, 2021)

Establishment of an indirect ELISA-based method involving the use of a multiepitope recombinant S protein to detect antibodies against canine coronavirus - Yun-Feng Hao; Shao-Han Li; Guang-Zhi Zhang; Yi Xu; Guang-zong Long; Xiao-xiong Lu; Shang-Jin Cui; Tong Qin (Archives of Virology, 2021)

Species and geographic specificity between endophytic fungi and host supported by parasitic Cynomorium songaricum and its host Nitraria tangutorum distributed in desert - Shuang-Man Miao; Yan-Yan Zhang; Jin-Long Cui; Gang Zhang (Archives of Microbiology, 2021)

Simulated Sensitivity of Ozone Generation to Precursors in Beijing during a High O3 Episode - Meng Cui; Xingqin An; Li Xing; Guohui Li; Guiqian Tang; Jianjun He; Xin Long; Shuman Zhao (Advances in Atmospheric Sciences, 2021)

Experimental study on adsorption promotion and desorption restrain of gas-containing coal in low-temperature environment - Fakai Wang; Xuelong Li; Bo Cui; Jian Hao; Xin Gao; Kun Long; Peng Chen; Sheng Wang (Arabian Journal of Geosciences, 2021)

Stable isotopes and chloride ion of precipitation events in the northeastern Tibetan Plateau, China - Bu-li Cui; Dong-sheng Li; Bao-fu Jiang; Ying Wang; Ya-xuan Wang; Long-sheng Wang; Xiao-yan Li (Journal of Mountain Science, 2021)

Global patterns in leaf stoichiometry across coastal wetlands - Yu‐Kun Hu; Xu‐Yan Liu; Nian‐Peng He; Xu Pan; Song‐Yuan Long; Wei Li; Man‐Yin Zhang; Li‐Juan Cui (Global Ecology and Biogeography, 2021)
Aim Coastal wetlands provide crucial ecosystem functions and services, such as coastal protection, nutrient retention and C sequestration. Despite the important roles in global C, N and P cycling, the global variation in leaf stoichiometry across coastal wetlands remains unclear. Location Global. Time period 1980–2018. Major taxa studied Vascular plants. Methods By compiling a global dataset of 698 data records in 205 sites, we carried out systematic analyses of the world‐wide trends and their determinants of leaf element contents and ratios of plants across coastal wetlands. Results Leaf N and P contents increased significantly, but C:N, C:P and N:P ratios decreased with increasing latitude in coastal wetlands. The mean annual temperature was the predominant driver of leaf N, P and C:N, whereas soil N:P was a good predictor of leaf C:P and N:P ratios. Furthermore, N increased faster with P in plant leaves of coastal wetlands compared with terrestrial ecosystems. Within coastal wetlands, herb‐dominated salt marshes had a significantly higher leaf P content, lower leaf N:P ratio and lower scaling exponent of leaf N to P than tree‐dominated mangroves. Main conclusions The similar latitudinal patterns of leaf stoichiometry in coastal wetlands compared with terrestrial ecosystems reflected the similar influences of temperature. However, different slopes of leaf P and N:P ratios and N and P scaling relationships between these two ecosystems suggested that different salinity and tidal inundation levels result in different strategies of N and P use in coastal wetland plants. These differences in leaf stoichiometry between ecosystems and between different types of coastal wetlands might need to be emphasized in future biogeochemical modelling owing to their different roles in global nutrient and carbon cycling.

Nanomaterials for Airborne Virus Inactivation: A Short Review - Rong Li; Long Cui; Meijuan Chen; Yu Huang (Aerosol Science and Engineering, 2021)

Establishment and characterization of a cold‐sensitive neural cell line from the brain of tilapia ( Oreochromis niloticus ) - Yong Long; Ran Liu; Guili Song; Qing Li; Zongbin Cui (Journal of Fish Biology, 2021)
The aquaculture of tilapia ( Oreochromis sp .) is adversely affected by the sensitivity to cold stress. A large number of genes in tilapia were found to be regulated by cold stress, but their functions and mechanisms in cold tolerance remain largely unknown, partially due to the lack of a suitable in vitro model. An immortal neural cell line designated as tilapia brain neural (TBN) was established from brain tissue of the genetically improved farmed tilapia strain of Nile tilapia ( Oreochromis niloticus ). The TBN cells show a neuron‐like morphology at low density and form a fibroblast‐like monolayer at high density. Transcriptome profiling through RNA‐sequencing revealed that a total of 15,011 genes were expressed in the TBN cells. The TBN cells express a wide array of marker genes for neural cells. A comparative analysis of the featured genes among the 17 cell clusters isolated from the subventricular zone of mouse brain revealed the highest transcriptome similarity between the TBN cells and the transient amplifying progenitors (TAPs). The TBN cells tolerate relatively high culture temperatures, and the highest growth rate was observed for the cells cultured at 32°C compared with those at 30°C, 28°C and 26°C. Nonetheless, this cell line is cold sensitive. Exposure of the cells to 16°C or lower temperatures significantly decreased cell confluences and induced apoptosis. The TBN cells were more sensitive to cold stress than the ZF4 cells (embryonic zebrafish fibroblasts). Moreover, the TBN cells can be efficiently transfected through electroporation. This study provides an invaluable research tool to understand the nature of cold sensitivity of tilapia and to dissect the function and mechanism of genes in regulating cold tolerance of fish.

Resazurin as an indicator of reducing capacity for analyzing the physiologic status of deep-sea bacterium Photobacterium phosphoreum ANT-2200 - Jie Dai; Hongzhi Tang; Xuegong Li; Claire-Lise Santini; Wenpeng Cui; Na Liu; Xiaoqing Qi; Xuehua Cui; Alain Grossi; Philippe Notareschi; Wei-Jia Zhang; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Profiles and Source Apportionment of Nonmethane Volatile Organic Compounds in Winter and Summer in Xi’an, China, based on the Hybrid Environmental Receptor Model - Jian Sun; Zhenxing Shen; Yue Zhang; Wenting Dai; Kun He; Hongmei Xu; Zhou Zhang; Long Cui; Xuxiang Li; Yu Huang; Junji Cao (Advances in Atmospheric Sciences, 2021)

Design and Characterization of a Novel Hybrid Antimicrobial Peptide OM19R Based on Oncocin and MDAP-2 - Lei Liu; Jie Liu; Qi Cui; Bo-Yan Jia; Zhi-Hua Pei; Kokou Ayefounin Odah; Yi-Ming Wang; Wen-Long Dong; Ling-Cong Kong; Hong-Xia Ma (International Journal of Peptide Research and Therapeutics, 2020)

Microwave-assisted hydrothermal assembly of 2D copper-porphyrin metal-organic frameworks for the removal of dyes and antibiotics from water - Shiyin Zhao; Shun Li; Zhicheng Zhao; Yiping Su; Yangke Long; Zuquan Zheng; Daling Cui; Yong Liu; Chunfei Wang; Xuanjun Zhang; Zuotai Zhang (Environmental Science and Pollution Research, 2020)

Cortical morphometry alterations in brain regions involved in emotional, motor-control and self-referential processing in patients with functional constipation - Chunxin Hu; Li Liu; Lei Liu; Junwang Zhang; Yang Hu; Wenchao Zhang; Yueyan Ding; Yuanyuan Wang; Zhida Zhang; Karen M. von Deneen; Long Qian; Huaning Wang; et al. (Brain Imaging and Behavior, 2020)

Accumulation of Cu, Cd, Pb, Zn and total P from synthetic stormwater in 30 bioretention plants - Ying Mei; Hang Zhou; Long Gao; Yi-Ming Zuo; Kun-Hao Wei; Na-Qi Cui (Environmental Science and Pollution Research, 2020)

Differential relationship of fungal endophytic communities and metabolic profiling in the stems and roots of Ephedra sinica based on metagenomics and metabolomics - Qi Zhang; Xiao-Zan Xue; Shuang-Man Miao; Jin-Long Cui; Xue-Mei Qin (Symbiosis, 2020)

Efficient removal of formaldehyde by polyethyleneimine modified activated carbon in a fixed bed - Dongdong Zhang; Mengxi Zhang; Feng Ding; Wei Liu; Long Zhang; Longzhe Cui (Environmental Science and Pollution Research, 2020)

Late Pleistocene environmental information on the Diexi paleo-dammed lake of the upper Minjiang River in the eastern margin of the Tibetan Plateau, China - Lan-sheng Wang; Xiao-qun Wang; Jun-hui Shen; Guan Yin; Jie Cui; Xiang-ning Xu; Zhi-long Zhang; Tao Wan; Li-wang Wen (Journal of Mountain Science, 2020)

Experimental Study on Unconsolidated Undrained Shear Strength Characteristics of Synthetic Cotton Fiber Reinforced Soil - Jian-long Liu; Tian-shun Hou; Ya-sheng Luo; Yi-xiang Cui (Geotechnical and Geological Engineering, 2020)

An approach for response prediction of a single pile subjected to tension load considering modulus degradation of soil - Chun-yu Cui; Shu-jian Wang; Qiang Liu; Yu-long Zhang (Geotechnical and Geological Engineering, 2020)

Amyloid precursor protein regulates 5-fluorouracil resistance in human hepatocellular carcinoma cells by inhibiting the mitochondrial apoptotic pathway - Xiao-long Wu; Ying Chen; Wen-cui Kong; Zhong-quan Zhao (Journal of Zhejiang University-SCIENCE B, 2020)

Line matching of wide baseline images in an affine projection space - Qiang Wang; Wei Zhang; Xiaolong Liu; Zhenxin Zhang; Muhammad Hasan Ali Baig; Guo Wang; Long He; Tiejun Cui (International Journal of Remote Sensing, 2020)

Component analysis and antiasthmatic effects of Huashanshen dripping pill - Shuli Man; Nina Cui; Xuanshuo Liu; Long Ma; Changxiao Liu; Wenyuan Gao (Medicinal Chemistry Research, 2020)

Cardiopulmonary Comorbidity, Radiomics and Machine Learning, and Therapeutic Regimens for a Cerebral fMRI Predictor Study in Psychotic Disorders - Xiao-Hui Wang; Angela Yu; Xia Zhu; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2019)

Urban VOC profiles, possible sources, and its role in ozone formation for a summer campaign over Xi’an, China - Jian Sun; Zhenxing Shen; Yue Zhang; Zhou Zhang; Qian Zhang; Tian Zhang; Xinyi Niu; Yu Huang; Long Cui; Hongmei Xu; Hongxia Liu; Junji Cao; et al. (Environmental Science and Pollution Research, 2019)

Erosion and transport mechanisms of mine waste along gullies - Xing-hua Zhu; Yi-fei Cui; Jian-bing Peng; Cheng Jiang; Wei-long Guo (Journal of Mountain Science, 2019)

Benzene metabolite 1,2,4-benzenetriol changes DNA methylation and histone acetylation of erythroid-specific genes in K562 cells - Chun-Hong Yu; Yang Li; Xiao Zhao; Shui-Qing Yang; Lei Li; Ning-Xuan Cui; Long Rong; Zong-Chun Yi (Archives of Toxicology, 2019)

Gene expression profiles of HTR8-S/Vneo cells after changes in ABCA1 expression - Chengmao Xie; Xiaohui Cai; Xiaoju Wang; Li Lin; Yan Long; Xin Cui (Functional & Integrative Genomics, 2018)

Apparent permeability and representative size of shale: a numerical study on the effects of organic matter - Jiangfeng Cui; Long Cheng; Lei Li (Computational Geosciences, 2018)

DJ-1 is involved in epigenetic control of sphingosine-1-phosphate receptor expression in vascular neointima formation - Kang Pa Lee; Suji Baek; Seung Hyo Jung; Long Cui; Donghyen Lee; Dong-Youb Lee; Wahn Soo Choi; Hyun Woo Chung; Byeong Han Lee; Bokyung Kim; Kyung Jong Won (Pflügers Archiv - European Journal of Physiology, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

A loop mediated isothermal amplification (LAMP) assay for rapid and reliable detection of Anguina wevelli, a grass parasitic nematode - Lu-zhen Yu; Shao-yi Song; Cui Yu; Long-jun Qi; Zi-xiang Yu; Bin-bin Jiao; Juan Yang (European Journal of Plant Pathology, 2018)

Soybean and cottonseed meals are good candidates for fishmeal replacement in the diet of juvenile Macrobrachium nipponense - Yu-Juan Huang; Nan-Nan Zhang; Wu-Jiang Fan; Yan-Yan Cui; Samwel Mchele Limbu; Fang Qiao; Yun-Long Zhao; Li-Qiao Chen; Zhen-Yu Du; Dong-Liang Li (Aquaculture International, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

A preliminary study on ore-forming environments of Xianglushan-type iron deposit and the weathering mineralization of Emeishan basalt in Guizhou Province, China - Guofan Cheng; Youping Liu; Hansheng Long; Tao Cui; Ning Yu (Acta Geochimica, 2017)

The In vitro/vivo Evaluation of Prepared Gastric Floating Tablets of Berberine Hydrochloride - Jun Ji; Xin He; Xiao-Lin Yang; Wen-Juan Du; Cheng-Long Cui; Ling Wang; Xue Wang; Chun-Feng Zhang; Chang-Run Guo (AAPS PharmSciTech, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

Similar behavior, different mechanisms: the research of the style bending of Alpinia species - Zhi-Long Su; Xian-Liang Cui; Li Li; Qing-Jun Li; Yin-Ling Luo (Acta Physiologiae Plantarum, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

iTRAQ-Based Comparative Proteomics Analysis of the Fruiting Dikaryon and the Non-fruiting Monokaryon of Flammulina velutipes - Jing-Yu Liu; Ming-chang Chang; Jun-long Meng; Cui-ping Feng; Yong-nan Liu (Current Microbiology, 2017)

Pusillimonas caeni sp. nov., isolated from a sludge sample of a biofilm reactor - Long Jin; So-Ra Ko; Yingshun Cui; Chang Soo Lee; Hee-Mock Oh; Chi-Yong Ahn; Hyung-Gwan Lee (Antonie van Leeuwenhoek, 2017)

P450-mediated detoxification of botanicals in insects - Sufen Cui; Lei Wang; Long Ma; Xueqing Geng (Phytoparasitica, 2016)

Influences of plant type on bacterial and archaeal communities in constructed wetland treating polluted river water - Yan Long; Hao Yi; Sili Chen; Zhengke Zhang; Kai Cui; Yongxin Bing; Qiongfang Zhuo; Bingxin Li; Shuguang Xie; Qingwei Guo (Environmental Science and Pollution Research, 2016)

Combined treatment with parathyroid hormone (1–34) and beta-tricalcium phosphate had an additive effect on local bone formation in a rat defect model - Zhou-Shan Tao; Kai-kai Tu; Zheng-Liang Huang; Qiang Zhou; Tao Sun; Hong-Ming Xu; Yu-Long Zhou; Yang-Xun Lv; Wei Cui; Lei Yang (Medical & Biological Engineering & Computing, 2016)

A graphical model for haloanhydrite components and P-wave velocity: A case study of haloanhydrites in Amu Darya Basin - Tong-Cui Guo; Hong-Jun Wang; Long-Xin Mu; Xing-Yang Zhang; Zhi Ma; Yu Tian; Hao-Chen Li (Applied Geophysics, 2016)

Erratum to: Progressive changes of orexin system in a rat model of 6-hydroxydopamine-induced Parkinson’s disease - Long-Biao Cui; Bo-Wei Li; Xiao-Hang Jin; Lin Zhao; Juan Shi (Neuroscience Bulletin, 2016)

Levels, congener profile and inventory of polychlorinated biphenyls in sediment from the Songhua River in the vicinity of cement plant, China: a case study - Song Cui; Qiang Fu; Yi-Fan Li; Wen-long Li; Tian-xiao Li; Min Wang; Zhen-xiang Xing; Lu-ji Zhang (Environmental Science and Pollution Research, 2016)

Northern-Hemisphere snow cover patterns and formation conditions in winter 2007 and 2012 - Hongyan Cui; Fangli Qiao; Qi Shu; Long Yu (Journal of Ocean University of China, 2016)

Sustainability of in situ remediation of Cu- and Cd-contaminated soils with one-time application of amendments in Guixi, China - Hongbiao Cui; Yuchao Fan; Lei Xu; Jing Zhou; Dongmei Zhou; Jingdong Mao; Guodong Fang; Long Cang; Zhenqiu Zhu (Journal of Soils and Sediments, 2016)

Petrogenesis and geodynamic significance of the Ganhe Formation lavas, eastern Great Xing'an Range, China : Evidence from geochemistry and geochronology - A‐lei Gu; Jing‐gui Sun; Ling‐an Bai; Yong Zhang; Pei‐long Cui; Peng Chai; Ke‐qiang Zhao; Qing‐long Sun; Liang Ren; Yan‐jun Chen; Jun‐quan Zhu (Island Arc, 2016)
Mesozoic volcanic rocks are widespread throughout the Great Xing'an Range of northeastern China . However, there has been limited investigation into the age and petrogenesis of the Mesozoic volcanics in the eastern Great Xing'an Range. According to our research, the volcanic rocks of the Dayangshu Basin, eastern Great Xing'an Range are composed mainly of trachybasalt, basaltic andesite, and basaltic trachyandesite, with minor intermediate–basic pyroclastic rocks. In this study, the geochemistry and geochronology of the Mesozoic volcanic rocks are presented in order to discuss the petrogenesis and tectonic setting of the Ganhe Formation in the Dayangshu Basin. Zircon U–Pb dating by laser ablation inductively coupled plasma–mass spectrometry indicates that the Mesozoic lavas formed during the late Early Cretaceous (114.3–108.8 Ma). This suite of rocks exhibits a range of geochemical signatures indicating subduction‐related genesis, including: (i) calc‐alkaline to high‐K calc‐alkaline major element compositions; (ii) enrichment of large ion lithophile elements (e.g. Rb, Ba, K) and light rare earth elements (LREEs/HREEs =7.33–9.85); and (iii) weak depletion in high field strength elements (e.g. Nb, Ta, Ti). Furthermore, Sr–Nd–Pb isotopic data yield initial 87 Sr/ 86 Sr values of 0.70450–0.70463, positive ε Nd (t) values of +1.8 to +3.3, and a mantle‐derived lead isotope composition. Combined with the regional tectonic evolution, the results of this study suggest that the Ganhe Group lavas are derived from decompression melting of a metasomatized (enriched) lithospheric mantle, related to asthenospheric upwelling, which resulted from lithospheric mantle delamination and produced extension of the continental margin following the subduction of the Paleo‐ Pacific Plate.

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Geological difficulties and countermeasures for socket diaphragm walls in weathered granite in Shenzhen, China - Qing-Long Cui; Huai-Na Wu; Shui-Long Shen; Ye-Shuang Xu (Bulletin of Engineering Geology and the Environment, 2016)

Molecular and pathogenicity characterization of Gallid herpesvirus 2 newly isolated in China from 2009 to 2013 - Yan-ping Zhang; Hong-chao Lv; Ke-yan Bao; Yu-long Gao; Hong-lei Gao; Xiao- le Qi; Hong-yu Cui; Yong-qiang Wang; Kai Li; Li Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2016)

Origin and evolution of ore fluids in the late Mesozoic Naozhi epithermal Au–Cu deposit, Yanbian area, Northeast China: evidence from fluid inclusion and isotopic geochemistry - A-Lei Gu; Lan-jing Men; Jing-Gui Sun; Keisuke Nagao; Ling-An Bai; Long-pei Cui; Peng Chai; Yan-jun Chen; Jun-quan Zhu (Arabian Journal of Geosciences, 2016)

Trend of water resource amount, drought frequency, and agricultural exposure to water stresses in the karst regions of South China - Long Wan; Jinxing Zhou; Hongyan Guo; Ming Cui; Yuguo Liu (Natural Hazards, 2016)

A novel Halomonas ventosae-specific virulent halovirus isolated from the Qiaohou salt mine in Yunnan, Southwest China - Chao-Qun Fu; Qin Zhao; Zhi-Ying Li; Yong-Xia Wang; Shi-Ying Zhang; Yong-Hong Lai; Wei Xiao; Xiao-Long Cui (Extremophiles, 2016)

Retraction Note to: Genetic variations in the KIR gene family may contribute to susceptibility to ankylosing spondylitis: a meta-analysis - Hai-Ning Zuo; Zhi-Long Wang; Dao-Ran Cui; Da-Jiang Xin (Molecular Biology Reports, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Erythropoietin Attenuates the Apoptosis of Adult Neurons After Brachial Plexus Root Avulsion by Downregulating JNK Phosphorylation and c-Jun Expression and Inhibiting c-PARP Cleavage - Kai Li; Rang-Juan Cao; Xiao-Juan Zhu; Xing-Yu Liu; Long-Yun Li; Shu-Sen Cui (Journal of Molecular Neuroscience, 2015)

Isolation and full-genome sequence of two reticuloendotheliosis virus strains from mixed infections with Marek’s disease virus in China - Ke-yan Bao; Yan-ping Zhang; Hui-wen Zheng; Hong-chao Lv; Yu-long Gao; Jing-fei Wang; Hong-lei Gao; Xiao-le Qi; Hong-yu Cui; Yong-qiang Wang; Xian-gang Ren; Xiao-mei Wang; et al. (Virus Genes, 2015)

A bellow pressure fiber optic sensor for static ice pressure measurements - Li-Qin Cui; Xin Long; Jian-Min Qin (Applied Geophysics, 2015)

Chinese karst geology and measures to prevent geohazards during shield tunnelling in karst region with caves - Qing-Long Cui; Huai-Na Wu; Shui-Long Shen; Ye-Shuang Xu; Guan-Lin Ye (Natural Hazards, 2015)

Arenimonas taoyuanensis sp. nov., a novel bacterium isolated from rice-field soil in China - Shi-Ying Zhang; Wei Xiao; Yun-Sheng Xia; Yong-Xia Wang; Xiao-Long Cui; Nai-Ming Zhang (Antonie van Leeuwenhoek, 2015)

Association mapping of salinity and alkalinity tolerance in improved japonica rice (Oryza sativa L. subsp. japonica Kato) germplasm - Di Cui; Chang-ying Xu; Chun-gang Yang; Qi-xing Zhang; Jun-guo Zhang; Xiao-ding Ma; Yong-li Qiao; Gui-lan Cao; San-yuan Zhang; Long-zhi Han (Genetic Resources and Crop Evolution, 2015)

Effect of zero-valent iron on the start-up performance of anaerobic ammonium oxidation (anammox) process - Long-Fei Ren; Shou-Qing Ni; Cui Liu; Shuang Liang; Bo Zhang; Qiang Kong; Ning Guo (Environmental Science and Pollution Research, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Genome-Wide Analysis of the C3H Zinc Finger Transcription Factor Family and Drought Responses of Members in Aegilops tauschii - An-Long Jiang; Zhao-Shi Xu; Guang-Yao Zhao; Xiao-Yu Cui; Ming Chen; Lian-Cheng Li; You-Zhi Ma (Plant Molecular Biology Reporter, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Selenium Promotes the Growth and Photosynthesis of Tomato Seedlings Under Salt Stress by Enhancing Chloroplast Antioxidant Defense System - Ming Diao; Long Ma; Jianwei Wang; Jinxia Cui; Aifei Fu; Hui-ying Liu (Journal of Plant Growth Regulation, 2014)

RETRACTED ARTICLE: Genetic variations in the KIR gene family may contribute to susceptibility to ankylosing spondylitis: a meta-analysis - Hai-Ning Zuo; Zhi-Long Wang; Dao-Ran Cui; Da-Jiang Xin (Molecular Biology Reports, 2014)

AGGF1 protects from myocardial ischemia/reperfusion injury by regulating myocardial apoptosis and angiogenesis - Yu Liu; Hui Yang; Lina Song; Nan Li; Qiu-Yue Han; Cui Tian; Erhe Gao; Jie Du; Yun-Long Xia; Hui-Hua Li (Apoptosis, 2014)

Halomonas qiaohouensis sp. nov., isolated from salt mine soil in southwest China - Yong-Xia Wang; Wei Xiao; Ming-Hua Dong; Qin Zhao; Zhi-Ying Li; Yong-Hong Lai; Xiao-Long Cui (Antonie van Leeuwenhoek, 2014)

Assessment of gene flow from glyphosate-resistant transgenic soybean to conventional soybean in China - Wen-Kun Huang; Huan Peng; Gao-Feng Wang; Jiang-Kuan Cui; Lin-Feng Zhu; Hai-Bo Long; De-Liang Peng (Acta Physiologiae Plantarum, 2014)

Molecular cloning and characterization of 5-enolpyruvylshikimate-3-phosphate synthase gene from Convolvulus arvensis L. - Zhao-Feng Huang; Chao-Xian Zhang; Hong-Juan Huang; Shou-Hui Wei; Yan Liu; Hai-Lan Cui; Jing-Chao Chen; Long Yang; Jin-Yi Chen (Molecular Biology Reports, 2014)

Importance of Functional Ingredients in Yak Milk-Derived Food on Health of Tibetan Nomads Living Under High-Altitude Stress: A Review - Xusheng Guo; Ruijun Long; Michael Kreuzer; Luming Ding; Zhanhuan Shang; Ying Zhang; Yang Yang; Guangxin Cui (Critical Reviews in Food Science and Nutrition, 2014)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

Comparative proteomic profiling during ovarian development of the shrimp Metapenaeus ensis - Ju Cui; Long Tao Wu; Ka Hou Chu (Molecular Biology Reports, 2014)

Oldest zircon xenocryst (4.17 Ga) from the North China Craton - Pei-Long Cui; Jing-Gui Sun; De-Ming Sha; Xi-Jing Wang; Peng Zhang; A-Lei Gu; Zhong-Yu Wang (International Geology Review, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Gene transfer and mutagenesis mediated by Sleeping Beauty transposon in Nile tilapia (Oreochromis niloticus) - Xiaozhen He; Jie Li; Yong Long; Guili Song; Peiyong zhou; Qiuxiang Liu; Zuoyan Zhu; Zongbin Cui (Transgenic Research, 2013)

Zircon U–Pb–Hf isotopes and bulk-rock geochemistry of gneissic granites in the northern Jiamusi Massif, Central Asian Orogenic Belt: implications for Middle Permian collisional orogeny and Mesoproterozoic crustal evolution - Pei-Long Cui; Jing-Gui Sun; Shi-Jiong Han; Peng Zhang; Yong Zhang; Ling-An Bai; A-Lei Gu (International Geology Review, 2013)

New precursor of tetraterpenoids from the soft coral Sarcophyton glaucum - Cui-Xian Zhang; Xi-Xin He; Jun Zhang; Qiong Guo; Ling-Fang Lei; Jing-Yu Su; Long-Mei Zeng (Natural Product Research, 2013)

Duration of sucrose preculture is critical for shoot regrowth of in vitro-grown apple shoot-tips cryopreserved by encapsulation-dehydration - Chao-Hong Feng; Zhen-Hua Cui; Bai-Quan Li; Long Chen; Yan-Li Ma; Yan-Hua Zhao; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Immobilization of foreign protein into polyhedra of Bombyx mori nucleopolyhedrovirus (BmNPV) - Xing-wei Xiang; Rui Yang; Lin Chen; Xiao-long Hu; Shao-fang Yu; Cui-ping Cao; Xiao-feng Wu (Journal of Zhejiang University-SCIENCE B, 2012)

Isolation and Identification of Endophytic Fungi in Roots of Nine Holcoglossum Plants (Orchidaceae) Collected from Yunnan, Guangxi, and Hainan Provinces of China - Xiao-Ming Tan; Xiao-Mei Chen; Chun-Lan Wang; Xiao-Hua Jin; Jin-Long Cui; Juan Chen; Shun-Xing Guo; Li-Fang Zhao (Current Microbiology, 2012)

Overexpression of a Wheat CCaMK Gene Reduces ABA Sensitivity of Arabidopsis thaliana During Seed Germination and Seedling Growth - Cui Yang; Aili Li; Yongliang Zhao; Zenglin Zhang; Yuanfang Zhu; Xiaomei Tan; Shuaifeng Geng; Hanzi Guo; Xueyong Zhang; Zhensheng Kang; Long Mao (Plant Molecular Biology Reporter, 2011)

Antitumor and antimicrobial activities of endophytic fungi from medicinal parts of Aquilaria sinensis - Jin-long Cui; Shun-xing Guo; Pei-gen Xiao (Journal of Zhejiang University-SCIENCE B, 2011)

Fluid Dynamics Analysis of a Novel Micropatterned Cell Bioreactor - Yuhong Cui; Bo Huo; Shujin Sun; Fan Yang; Yuxin Gao; Jun Pan; Mian Long (Annals of Biomedical Engineering, 2011)

Antimicrobial Activity and Biodiversity of Endophytic Fungi in Dendrobium devonianum and Dendrobium thyrsiflorum from Vietman - Yong-Mei Xing; Juan Chen; Jin-Long Cui; Xiao-Mei Chen; Shun-Xing Guo (Current Microbiology, 2011)

Molecular analysis and heavy metal detoxification of ABCC1/MRP1 in zebrafish - Yong Long; Qing Li; Zongbin Cui (Molecular Biology Reports, 2011)

IL-6/STAT3/TFF3 signaling regulates human biliary epithelial cell migration and wound healing in vitro - Gui-xing Jiang; Xiang-yu Zhong; Yun-fu Cui; Wei Liu; Sheng Tai; Zhi-dong Wang; Yu-guang Shi; Shi-yong Zhao; Chun-long Li (Molecular Biology Reports, 2010)

Progressive changes of orexin system in a rat model of 6-hydroxydopamineinduced Parkinson’s disease - Cui Long-Biao; Li Bo-Wei; Jin Xiao-Hang; Zhao Lin; Shi Juan (Neuroscience Bulletin, 2010)

Zhihengliuella salsuginis sp. nov., a moderately halophilic actinobacterium from a subterranean brine - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhu-Xiang Liu; Qi-Hui Chen; Jian-Wu He; Xiao-Long Cui; Wen-Jun Li (Extremophiles, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

Virgibacillus zhanjiangensis sp. nov., a marine bacterium isolated from sea water - Qing-Zhong Peng; Jun Chen; Yu-Qin Zhang; Qi-Hui Chen; De-Jiao Peng; Xiao-Long Cui; Wen-Jun Li; Yi-Guang Chen (Antonie van Leeuwenhoek, 2009)

Halobacillus hunanensis sp. nov., a moderately halophilic bacterium isolated from a subterranean brine - Qing-Zhong Peng; Qing-Jing Peng; Yu-Qin Zhang; Zhu-Xiang Liu; Yong-Xia Wang; Wen-Jun Li; Xiao-Long Cui; Yi-Guang Chen (Antonie van Leeuwenhoek, 2009)

Virgibacillus litoralis sp. nov., a moderately halophilic bacterium isolated from saline soil - Yi-Guang Chen; Zhu-Xiang Liu; De-Jiao Peng; Yu-Qin Zhang; Yong-Xia Wang; Shu-Kun Tang; Wen-Jun Li; Xiao-Long Cui; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Alteromonas halophila sp. nov., a new moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Huai-Dong Xiao; Shu-Kun Tang; Yu-Qin Zhang; Entomack Borrathybay; Xiao-Long Cui; Wen-Jun Li; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Halobacillus naozhouensis sp. nov., a moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Zhi-Xiong Liu; Yu-Qin Zhang; You-Xiang Zhang; Shu-Kun Tang; Entomack Borrathybay; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Arthrobacter halodurans sp. nov., a new halotolerant bacterium isolated from sea water - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhao-Yang Li; Lang-Bo Yi; Yong-Xia Wang; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Halomonas sediminis sp. nov., a new halophilic bacterium isolated from salt-lake sediment in China - Heng-Yu Huang; Yi-Guang Chen; Yong-Xia Wang; Ji-Hui Liu; Shu-Kun Tang; Qian Peng; Meng-Liang Wen; Hong Yu; Xiao-Long Cui (Extremophiles, 2008)

Nitrous oxide emissions from two alpine meadows in the Qinghai–Tibetan Plateau - Yangong Du; Yingguang Cui; Xingliang Xu; Dongying Liang; Ruijun Long; Guangmin Cao (Plant and Soil, 2008)

Analysis of synonymous codon usage and evolution of begomoviruses - Xiao-zhong Xu; Qing-po Liu; Long-jiang Fan; Xiao-feng Cui; Xue-ping Zhou (Journal of Zhejiang University-SCIENCE B, 2008)

Salinicoccus salitudinis sp. nov., a new moderately halophilic bacterium isolated from a saline soil sample - Yi-Guang Chen; Xiao-Long Cui; Wen-Jun Li; Li-Hua Xu; Meng-Liang Wen; Qian Peng; Cheng-Lin Jiang (Extremophiles, 2008)

d-Galactose toxicity in mice is associated with mitochondrial dysfunction: protecting effects of mitochondrial nutrient R-alpha-lipoic acid - Jiangang Long; Xuemin Wang; Hongxiang Gao; Zhi Liu; Changsheng Liu; Mingyong Miao; Xu Cui; Lester Packer; Jiankang Liu (Biogerontology, 2007)

Identification and Characterization of the Human SCAN Domain Zinc-Finger Gene ZNF449 - Kuntian Luo; Jie Li; Yanhui Cui; Meng Xu; Jian Yuan; Wenwen Tang; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Study of removal effect on Mesocyclops leukarti with oxidants - Jin-long Zuo; Fu-yi Cui; Tao Lin (Journal of Zhejiang University-SCIENCE B, 2006)

High Frequency of Shoot Regeneration from Hypocotyls and Stem Segments of Antirrhinum majus (Snapdragon) - Min-Long Cui; Kenji Takayanagi; Takashi Handa (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Cloning of human myeloid-associated differentiation marker (MYADM) gene whose expression was up-regulated in NB4 cells induced by all-trans retinoic acid - Wanchang Cui; Long Yu; Hua He; Yaya Chu; Jie Gao; Bo Wan; Lisha Tang; Shouyuan Zhao (Molecular Biology Reports, 2001)

Cloning and Tissue Expressional Characterization of a Full-Length cDNA Encoding Human Neuronal Protein P17.3 - Yingyu Cui; Long Yu; Ruomu Gong; Min Zhang; Yuxin Fan; Peng Yue; Shouyuan Zhao (Biochemical Genetics, 1999)